Optical laminate
Patent Information
- Application Number
- JP2024016970
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2024-02-07
- Publication Date
- 2025-02-14
AI Technical Summary
【0012】 本発明の光学積層体によれば、偏光子の端部が盛り上がることを抑制できる。
Smart Images

Figure 2025022695000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate. [Background technology]
[0002] An optical laminate including a polarizer made of a polyvinyl alcohol-based resin film is known. Patent Document 1 discloses an optical laminate having a structure for protecting a polarizer. Specifically, the optical laminate disclosed in Patent Document 1 includes a polarizer protective film for protecting the polarizer laminated on the polarizer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2022-101448 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present inventors have found that an optical laminate having the above-mentioned configuration for protecting a polarizer causes a phenomenon in which the end of the polarizer swells in a high-temperature environment. There is a demand for an optical laminate that can suppress the occurrence of this phenomenon. [Means for solving the problem]
[0005] The present invention includes the following inventions. [Invention 1] An optical laminate including, in this order, an optical film including a pressure-sensitive adhesive layer, a polarizer in which a dichroic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film, a first attachment layer, a retardation plate, and a second attachment layer, the pressure-sensitive adhesive layer side of the optical film is in direct contact with the polarizer, The polarizer and the first attachment layer are in direct contact with each other, The layer constituted by the first bonding layer, the retardation plate, and the second bonding layer has an absorbance of 0.1 or more for light having a wavelength of 340 nm. Optical laminate.
[0006] [Invention 2] The boron content of the polarizer is 0.5% by mass or more. The optical laminate according to [Invention 1].
[0007] [Invention 3] The luminosity-corrected single transmittance of the polarizer is 41% or more; The luminosity-corrected polarization degree of the polarizer is 99.5% or more. The optical laminate according to [Invention 1] or [Invention 2].
[0008] [Invention 4] The retardation plate is made of a liquid crystal cured layer. The optical laminate according to any one of [Invention 1] to [Invention 3].
[0009] [Invention 5] The retardation plate is a λ / 4 retardation plate exhibiting reverse wavelength dispersion. The optical laminate according to any one of [Invention 1] to [Invention 4].
[0010] [Invention 6] The first attachment layer is a pressure-sensitive adhesive layer. The optical laminate according to any one of [Invention 1] to [Invention 5].
[0011] [Invention 7] The first bonding layer contains an ultraviolet absorbing agent. The optical laminate according to any one of [Invention 1] to [Invention 6]. Effect of the Invention
[0012] According to the optical laminate of the present invention, it is possible to prevent the end portion of the polarizer from swelling up. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view showing a layer structure of one embodiment of an optical laminate. [Diagram 2] FIG. 2 is a cross-sectional view showing the layer structure of another example of the optical laminate. [Diagram 3] FIG. 3 is an explanatory diagram for explaining the microscopic Raman spectroscopic analysis of the polarizing plate according to this embodiment. [Figure 4] FIG. 4 is a schematic diagram illustrating an evaluation sample for performing an end swelling test. [Diagram 5] FIG. 5 is a graph showing an example of the measurement results in the edge swelling test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, one embodiment of the optical laminate will be described. FIG. 1 is a schematic cross-sectional view illustrating a layer configuration of an optical laminate 1 of the present embodiment. FIG. 2 shows an optical stack 2 including an image display element 40 .
[0015] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the drawings. (1) Optical laminate As shown in FIG. 1, the optical laminate 1 includes an optical film 109 including a pressure-sensitive adhesive layer, a polarizer 101, a first bonding layer 30a, a retardation plate 20, and a second bonding layer 30b in this order. In FIG. 1, a surface protection film for protecting the surface of the polarizer 101 is provided as the optical film having a pressure-sensitive adhesive layer. For example, the surface protection film is an optical film in which a pressure-sensitive adhesive layer is formed on the surface of a resin film for a surface protection film. The optical film on which the pressure-sensitive adhesive layer is formed corresponds to the optical film including the pressure-sensitive adhesive layer. The surface protection film may be a self-adhesive optical film. In this case, the self-adhesive optical film corresponds to the optical film including the pressure-sensitive adhesive layer.
[0016] For example, the surface protective film is configured so that it can be peeled off together with the pressure-sensitive adhesive layer from the polarizer 101. In this case, the optical laminate 1 is used in a state in which the surface protective film is removed together with the pressure-sensitive adhesive layer.
[0017] For example, the surface protection film is configured so that the resin film for surface protection film can be peeled off while the adhesive layer remains attached to the polarizer 101. In this case, the optical laminate 1 is used in a state in which the resin film for surface protection film is removed and the adhesive layer is laminated on the polarizer 101. The adhesive layer laminated on the polarizer 101 after the resin film for surface protection film is removed is used to bond the optical laminate 1 and a component disposed on the opposite side of the retardation plate 20 with respect to the polarizer 101. For this reason, the adhesive layer is different from a protective layer that may be laminated on the polarizer for the purpose of protecting the polarizer. The above-mentioned component disposed on the opposite side of the retardation plate 20 with respect to the polarizer 101 may be, for example, a front plate or the like.
[0018] In the optical laminate 1, the optical film 109 including the adhesive layer and the polarizer 101 are in direct contact with each other via the adhesive layer. Furthermore, in the optical laminate 1, the surface of the polarizer 101 opposite to the surface directly in contact with the optical film 109 via the adhesive layer is in direct contact with the first bonding layer 30a. That is, the optical laminate 1 does not include a protective film (hereinafter, sometimes referred to as a "polarizer protective film") or a protective layer that protects the polarizer 101. Note that the polarizer protective film is used in the optical laminate in a state where it is laminated on the polarizer, and is different from the optical film 109 including the adhesive layer that is peeled off during use. As with the polarizer protective film, the protective layer is also used in the optical laminate in a state where it is laminated on the polarizer. As described above, the protective layer is different from the adhesive layer that remains laminated on the polarizer 101 after the resin film for the surface protective film is removed from the surface protective film. In this way, the polarizer protective film and the protective layer are different from the optical film 109 including the adhesive layer that is peeled off during use.
[0019] Here, the polarizer protective film that is not provided in the optical laminate 1 will be described. A thermoplastic resin film is used as the polarizer protective film. The polarizer protective film is laminated to the polarizer, for example, by the self-adhesiveness of the protective film. The polarizer protective film is laminated, for example, via an adhesive layer or a pressure-sensitive adhesive layer.
[0020] The protective layer that is not provided in the optical laminate 1 will be described. A polymer with a high crosslinking density is used as the protective layer. Another example of the protective layer is a water-soluble polymer with high hydrophilic interaction. The protective layer is laminated on the polarizer without an adhesive layer or a pressure-sensitive adhesive layer.
[0021] The optical laminate 1 may have one or more other layers between the first bonding layer 30a, the retardation plate 20, and the second bonding layer 30b. The other layers that the optical laminate 1 may have are other than the polarizer protective film and the protective layer.
[0022] The retardation plate 20 includes, for example, a first liquid crystal cured layer 201, a third bonding layer 30c, and a second liquid crystal cured layer 202 in this order from the polarizer 101 side. For example, the retardation plate 20 is preferably a λ / 4 retardation plate exhibiting reverse wavelength dispersion, which will be described later.
[0023] As shown in FIG. 2, the optical laminate 2 includes a polarizer 101, a first bonding layer 30a, a retardation plate 20, and a second bonding layer 30b on the viewing side of the image display element 40. The polarizer 101, the first bonding layer 30a, the retardation plate 20, the second bonding layer 30b, and the image display element 40 are arranged in this order. The layers laminated on the viewing side of the image display element 40 can be the same as those in the optical laminate 1. The optical laminate 2 including the image display element 40 may further include an optical film 109 including a pressure-sensitive adhesive layer in direct contact with the polarizer 101 as in the optical laminate 1 shown in FIG. 1.
[0024] In the optical laminate 1, the thickness from the surface of the polarizer 101 on the optical film 109 side including the pressure-sensitive adhesive layer to the surface of the second bonding layer 30b on the opposite side to the retardation plate 20 is, for example, 20 μm or more and 50 μm or less. The upper limit of the above range is preferably 48 μm, more preferably 40 μm. The lower limit of the above range is preferably 25 μm, more preferably 28 μm. According to this embodiment, the thickness of the optical laminate can be reduced by not providing a protective film or protective layer that protects the polarizer 101. According to this embodiment, the thickness of the optical laminate can be reduced by adopting an optically anisotropic layer described later as a layer that exhibits retardation, compared to the case of adopting a retardation film.
[0025] The phenomenon that the end of the polarizer swells in a high-temperature environment is believed to be caused by the difference between the shrinkage rate of the polarizer and the shrinkage rate of the protective film. Specifically, the end swells because the shrinkage rate of the polarizer is greater than that of the protective film. For example, when a protective film is disposed on the surface of the polarizer opposite to the viewing side of the optical laminate, warping toward the polarizer side is likely to occur, and the end swells are likely to occur.
[0026] In this regard, the optical laminate of this embodiment does not include a protective film or protective layer for protecting the polarizer 101 (hereinafter, sometimes referred to as a "bare film"), and therefore the swelling at the end of the polarizer 101 can be suppressed. In detail, the optical laminate 1 of this embodiment has the polarizer 101, the first bonding layer 30a, and the retardation plate 20 laminated in this order. Furthermore, in the optical laminate 1 of this embodiment, the polarizer 101 and the first bonding layer 30a are in direct contact with each other. Therefore, the first bonding layer 30a can easily follow the contraction of the polarizer 101. This can suppress the swelling at the end of the polarizer 101.
[0027] The present inventors have also confirmed that in an optical laminate bonded to an image display element, the longer the distance from the image display element to the polarizer, the more likely the end bulge is to occur. In this regard, in the optical laminate of this embodiment, the thickness of the optical laminate can be reduced as described above, thereby shortening the distance from the image display element to the polarizer. This makes it possible to further suppress the end bulge.
[0028] In the optical laminate 1, the layer constituted by the first bonding layer 30a, the retardation plate 20, and the second bonding layer 30b has an absorbance of, for example, 0.1 or more and 5 or less for light having a wavelength of 340 nm. The upper limit of the absorbance is preferably 4.5, more preferably 3.5, even more preferably 3.0, and particularly preferably 2.5. The lower limit of the absorbance is preferably 0.5, more preferably 1.0, and even more preferably 2.0.
[0029] When the optical laminate 1 has other layers between the first bonding layer 30a, the retardation plate 20, and the second bonding layer 30b, it is preferable that the absorbance measured including the other layers is within the above range.
[0030] As an optical laminate, one containing an ultraviolet absorber and a light stabilizer in a protective film or protective layer that protects a polarizer is known. That is, weather resistance is imparted to the optical laminate by a protective film or protective layer. In contrast, the optical laminate of this embodiment does not have a protective film or protective layer that protects the polarizer 101, but the layer composed of the first bonding layer 30a, the retardation plate 20, and the second bonding layer 30b has an absorbance of 0.1 or more for light with a wavelength of 340 nm. This makes it difficult for the luminosity-corrected polarization degree Py in the optical laminate to decrease over time, so that the optical laminate of this embodiment has excellent weather resistance even though it is a bare film.
[0031] If the absorbance is 0.1 or less, degradation due to ultraviolet light reflected by the image display element is likely to occur. In this respect, the optical laminate of the present embodiment can suppress degradation due to ultraviolet light even though it is a bare film. Therefore, it is possible to suppress a decrease in the luminosity-corrected polarization degree Py that may occur due to degradation due to ultraviolet light.
[0032] In the optical laminate of this embodiment that does not have a protective film or protective layer for protecting the polarizer 101, if the absorbance is 5 or more, degradation due to heat becomes significant in a weather resistance test. In this regard, the optical laminate of this embodiment can suppress degradation due to heat even though it is a bare film. Therefore, it is possible to suppress an increase in luminous efficiency-corrected single transmittance Ty and a decrease in luminous efficiency-corrected polarization degree Py that may occur due to degradation due to heat.
[0033] It is preferable that at least one of the first bonding layer 30a, the retardation plate 20, and the second bonding layer 30b has ultraviolet absorbing properties in the optical laminate 1. In particular, it is particularly preferable that the first bonding layer 30a has ultraviolet absorbing properties.
[0034] When at least one of the first bonding layer 30a, the retardation plate 20, and the second bonding layer 30b has ultraviolet absorbing properties, a decrease in the luminosity-corrected polarization degree Py in the optical laminate is easily suppressed.
[0035] In particular, when the first bonding layer 30a contains ultraviolet absorbing properties, the ultraviolet ray can be absorbed by the layer disposed between the polarizer 101 and the retardation film 20, so that deterioration of the retardation film 20 can be suppressed.
[0036] The elements that constitute or can constitute the optical laminate 1 will be described in detail below. (2) Polarizer The polarizer 101 is an optical film (linear polarizer) that transmits linearly polarized light having a vibration plane perpendicular to the absorption axis when unpolarized light is incident on the polarizer 101. Specifically, the polarizer 101 is a polyvinyl alcohol-based resin film (hereinafter also referred to as a "PVA-based film") in which a dichroic dye is adsorbed and oriented.
[0037] The polyvinyl alcohol resin (hereinafter also referred to as "PVA resin") constituting the PVA-based film can be produced by saponifying a polyvinyl acetate-based resin. The polyvinyl acetate-based resin can be a copolymer of vinyl acetate and other monomers copolymerizable with vinyl acetate, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group. In this specification, "(meth)acryl" means either acrylic or methacrylic. The "(meth)" in (meth)acrylate has the same meaning.
[0038] The saponification degree of the PVA resin is usually about 85 to 100 mol%, preferably 98 mol% or more. The PVA resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the PVA resin is usually about 1000 to 10000, preferably about 1500 to 5000. The average polymerization degree of the PVA resin can be determined in accordance with JIS K 6726 (1994). If the average polymerization degree is less than 1000, it is difficult to obtain a preferable polarizing performance, and if it exceeds 10000, the film processability may be poor.
[0039] Polarizer 101 is typically manufactured through a process of uniaxially stretching a PVA-based film, a process of dyeing the PVA-based film with a dichroic dye to adsorb the dichroic dye, a process of treating the PVA-based film with the adsorbed dichroic dye with an aqueous boric acid solution to crosslink the film, and a process of washing the film with water after the crosslinking treatment with the aqueous boric acid solution (hereinafter also referred to as boric acid treatment).
[0040] The uniaxial stretching of the PVA-based film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during the boric acid treatment. Of course, the uniaxial stretching can be performed in the multiple stages shown here. For the uniaxial stretching, a method of uniaxially stretching in the film transport direction between rolls having different peripheral speeds, a method of uniaxially stretching in the film transport direction using a heated roll, or a method of stretching in the width direction using a tenter can be adopted. The uniaxial stretching may be performed by dry stretching in the air, or by wet stretching in which the PVA-based film is stretched in a swollen state using a solvent such as water. The stretching ratio is usually about 3 to 8 times.
[0041] Dyeing of a PVA-based film with a dichroic dye can be carried out, for example, by immersing the PVA-based film in an aqueous solution containing the dichroic dye. As the dichroic dye, specifically, iodine or a dichroic organic dye is used. It is preferable that the PVA-based film is immersed in water and swelled before the dyeing process.
[0042] When iodine is used as the dichroic dye, a method of dyeing a PVA-based film by immersing it in an aqueous solution containing iodine and potassium iodide is usually adopted. The content of iodine in this aqueous solution is usually about 0.01 to 1 part by mass per 100 parts by mass of water, and the content of potassium iodide is usually about 0.5 to 20 parts by mass per 100 parts by mass of water. The temperature of the aqueous solution used for dyeing is usually about 20 to 40°C. The immersion time in this aqueous solution (dyeing time) is usually about 20 to 1,800 seconds.
[0043] On the other hand, when a dichroic organic dye is used as the dichroic pigment, a method of immersing a PVA-based film in an aqueous solution containing a water-soluble dichroic organic dye is usually used for dyeing. The content of the dichroic organic dye in this aqueous solution is usually about 0.0001 to 10 parts by mass, preferably 0.001 to 1 part by mass, per 100 parts by mass of water. This aqueous dye solution may contain an inorganic salt such as sodium sulfate as a dyeing assistant. The temperature of the aqueous dichroic organic dye solution used for dyeing is usually about 20 to 80°C. The immersion time in this aqueous solution (dyeing time) is usually about 10 to 1,800 seconds.
[0044] The boric acid treatment after dyeing with a dichroic dye can be carried out by immersing the dyed PVA-based film in a boric acid-containing aqueous solution. The content of boric acid in the boric acid-containing aqueous solution is usually about 2 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. When iodine is used as the dichroic dye, the boric acid-containing aqueous solution preferably contains potassium iodide. The content of potassium iodide in the boric acid-containing aqueous solution is usually about 0.1 to 15 parts by mass, preferably 5 to 12 parts by mass, per 100 parts by mass of water. The immersion time in the boric acid-containing aqueous solution is usually about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the boric acid-containing aqueous solution is usually 50°C or higher, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0045] The PVA-based film after the boric acid treatment is usually washed with water. The washing can be performed, for example, by immersing the boric acid-treated PVA-based film in water. The temperature of the water in the washing is usually about 5 to 40° C. The immersion time is usually about 1 to 120 seconds.
[0046] After washing with water, the polarizer 101 is obtained by carrying out a drying treatment. The drying treatment can be carried out using a hot air dryer or a far infrared heater. The temperature of the drying treatment is usually about 30 to 100°C, and preferably 50 to 80°C. The time of the drying treatment is usually about 60 to 600 seconds, and preferably 120 to 600 seconds. The moisture content in the polarizer 101 is reduced to a practical level by the drying treatment. The moisture content is usually about 5 to 20 mass% and preferably 8 to 15 mass% with respect to the total mass of the polarizer 101. When the moisture content is 5 mass% or more, the polarizer 101 has sufficient flexibility, and therefore, damage or breakage after drying can be suppressed. When the moisture content is 20 mass% or less, the polarizer 101 has sufficient thermal stability.
[0047] In this manner, the polarizer 101 in which the dichroic dye is adsorbed and aligned on the PVA film can be manufactured. The polarizer 101 has a boron content of preferably 0.5% by mass or more, more preferably 1.5% by mass or more, even more preferably 2.5% by mass or more, and may be 3.5% by mass or more. When the boron content of the polarizer 101 is in the above-mentioned numerical range, polyvinyl alcohol molecular chains tend to be crosslinked with boric acid, that is, the polarizer 101 tends to have a high degree of crosslinking. When the polarizer 101 has a high degree of crosslinking, the weather resistance of the polarizer 101 can be improved. Therefore, the optical laminate 1 can be easily used in a state where the surface protective film as the optical film 109 including the pressure-sensitive adhesive layer is removed. The boron content of the polarizer 101 is preferably 5.5% by mass or less, more preferably 5.0% by mass or less, and even more preferably 4.5% by mass or less. When the boron content is 4.5% by mass or less, the shrinkage of the polarizer 101 caused by heating can be suppressed.
[0048] The "boric acid crosslinking index" of the polarizer 101 used in this embodiment is preferably high from the viewpoint of durability. The boric acid crosslinking index is preferably 0.5 or more, more preferably 0.8 or more, even more preferably 1.0 or more, and even more preferably 1.2 or more. In this specification, the "boric acid crosslinking index" means an index that indicates the extent to which polyvinyl alcohol molecular chains are crosslinked with boric acid in a polarizer made of a polyvinyl alcohol resin film or the like. The higher the value of the boric acid crosslinking index, the more advanced the boric acid crosslinking between the polyvinyl alcohol molecular chains is in the polarizer, and the boric acid crosslinking index of the polarizer 101 in such a range can stably hold iodine. As a result, it becomes easier to prevent the polarization degree of the polarizer 101 from decreasing, and the durability of the circular polarizing plate is easier to improve. The boric acid crosslinking index can be adjusted by changing the manufacturing conditions of the polarizer, such as the content of boric acid in the boric acid-containing aqueous solution, the temperature of the boric acid-containing aqueous solution, and the temperature of the drying process.
[0049] The boric acid crosslinking index of the polarizer 101 can be determined by performing micro-Raman spectroscopy. In the micro-Raman spectroscopy, a laser Raman spectrophotometer (product name: "NRS-5100", manufactured by JASCO Corporation) is used to measure the boric acid crosslinking index at a wave number of 780 cm of the polarizer. -1 Raman scattering intensity at 850 cm -1 The Raman scattering light intensity at each wavenumber was then calculated, and the Raman scattering light intensities at these wavenumbers were then divided (wavenumber 780 cm -1 Raman scattering intensity at 850 cm -1 The boric acid crosslinking index can be calculated by measuring the Raman scattering intensity at 100 nm.
[0050] FIG. 3 is an explanatory diagram for explaining microscopic Raman spectroscopy of the polarizing plate according to this embodiment. As shown in FIG. 3, in a laser Raman spectrophotometer, a laser beam is incident on an end face of a polarizer 101 so that the traveling direction of the laser beam X is perpendicular to the absorption axis direction of the polarizer 101. Here, the laser beam X is polarized in the thickness direction of the polarizer 101. The measurement position of the laser beam is set to the center position in the thickness direction of the polarizer 101. It is preferable to process the cross section of the polarizing plate using a microtome before the Raman spectroscopy measurement. Wave number 780 cm -1 The Raman scattering intensity at 850 cm means the Raman scattering intensity attributable to the bond between polyvinyl alcohol and boron. -1 The Raman scattered light intensity in this case means the Raman scattered light intensity attributable to polyvinyl alcohol.
[0051] The various conditions used in the above-mentioned microscopic Raman spectroscopic analysis are as follows: Excitation wavelength: 532nm Grating: 600 l / mm Slit width: 100×1000μm Aperture: φ40μm Objective lens: 100x Objective lens: 100x The luminosity-corrected polarization degree Py of the polarizer 101 is usually 95% or more, preferably 97% or more, more preferably 98% or more, even more preferably 98.7% or more, even more preferably 99.0% or more, particularly preferably 99.4% or more, and may be 99.9% or more. Considering the optical laminate 1 in a state in which the optical film 109 including the adhesive layer is removed, it is preferably 99.5% or more, more preferably 99.91% or more. The luminosity-corrected polarization degree Py of the polarizer may be 99.99% or less. The luminosity-corrected polarization degree Py can be calculated by performing luminosity correction on the obtained polarization degree using a spectrophotometer with an integrating sphere ("V7100" manufactured by JASCO Corporation) with a 2-degree visual field (C light source) of "JIS Z 8701". Increasing the luminosity-corrected polarization degree Py of the polarizer 101 is advantageous in terms of improving the function of the circular polarizer as an antireflection film and the durability of the circular polarizer. If the luminous efficiency-corrected polarization degree Py of the polarizer 101 is less than 95%, the polarizer may not function as an antireflection film. The luminous efficiency-corrected polarization degree Py can be measured by the method described below.
[0052] Increasing the luminosity-corrected polarization degree Py of the polarizer is advantageous in terms of improving the function of the optical laminate as an antireflection film and the durability of the optical laminate. If the luminosity-corrected polarization degree Py of the polarizer is less than 95%, the polarizer may not function as an antireflection film.
[0053] The thickness of the polarizer is 15 μm or less, preferably 13 μm or less, more preferably 10 μm or less. When the thickness of the polarizer is within this range, it is advantageous for thinning the optical laminate, and the retardation change amount can be more effectively suppressed. The thickness of the polarizer is usually 2 μm or more, preferably 3 μm or more, and may be, for example, 5 μm or more.
[0054] The luminosity-corrected single transmittance Ty of the polarizer 101 is usually 40% or more, preferably 41% or more, and more preferably 42% or more. The luminosity-corrected single transmittance Ty of the polarizer 101 is usually 50% or less, and may be 48% or less, 46% or less, 44% or less, or 43% or less. If the luminosity-corrected single transmittance Ty is excessively high, the luminosity-corrected polarization degree Py becomes too low, and the circular polarizer may not be able to function as an anti-reflection film. The luminosity-corrected single transmittance Ty can be measured by the method described below.
[0055] (3) Retardation plate The retardation plate 20 includes a layer that exhibits retardation, and the layer that exhibits retardation may be a retardation film formed by stretching a thermoplastic resin film, or may be an optically anisotropic layer (hereinafter also referred to as a "retardation film") made of an oriented polymer of a polymerizable liquid crystal compound.
[0056] The thickness of the retardation plate 20 is, for example, 1 μm or more and 10 μm or less. The upper limit of the above range is preferably 8 μm, and more preferably 6 μm. (3-1) Retardation film A composition containing a polymerizable liquid crystal compound (hereinafter also referred to as a "composition for forming a retardation film") is applied onto a transparent substrate to form an optically anisotropic layer made of an aligned polymer of the polymerizable liquid crystal compound, which is preferable in terms of being able to reduce the thickness and design wavelength dispersion characteristics as desired. The composition for forming a retardation film may further contain a solvent, a photopolymerization initiator, a photosensitizer, a polymerization inhibitor, a leveling agent, an adhesion improver, and the like.
[0057] The retardation film is usually formed by applying a retardation film-forming composition onto an alignment film formed on a substrate, and polymerizing the polymerizable liquid crystal compound contained in the retardation film-forming composition. The retardation film is usually a film in which the polymerizable liquid crystal compound is cured in an aligned state, and in order to generate a retardation in the viewing surface, it is necessary to be a cured film in which the polymerizable group is polymerized in a state in which the polymerizable liquid crystal compound is aligned horizontally relative to the substrate surface. In this case, if the polymerizable liquid crystal compound is a rod-shaped liquid crystal, a positive A plate is sufficient, and if the polymerizable liquid crystal compound is a disc-shaped liquid crystal, a negative A plate is sufficient.
[0058] The retardation film may include two or more layers of different optical anisotropy. In order to achieve a high level of anti-reflection function, it is sufficient to have a λ / 4 plate function (i.e., a π / 2 phase difference function) in the entire visible light range. Specifically, a reverse wavelength dispersion λ / 4 layer is preferable, or it is preferable to combine two or more types of retardation films with different orientations. For example, a retardation film having a λ / 2 plate function (i.e., a π phase difference function) and a retardation film having a λ / 4 plate function (i.e., a π / 2 phase difference function) may be combined. Furthermore, from the viewpoint of being able to compensate for the anti-reflection function in an oblique direction, it is preferable to further include a layer having anisotropy in the thickness direction (positive C plate). In addition, each optical anisotropy layer may have a tilt orientation or may form a cholesteric orientation state.
[0059] When the retardation plate 20 is formed by bonding two or more types of retardation films having different orientations, they can be bonded via a third bonding layer 30c. The λ / 4 function over the entire visible light range preferably satisfies the optical characteristics shown in the following formula (1), where Re(λ) is the in-plane retardation value for light with a wavelength of λ nm, and more preferably satisfies the optical characteristics shown in the following formulas (1), (2), and (3).
[0060] 100nm <Re(550)<160nm (1) (In the formula, Re(550) represents the in-plane phase difference value (in-plane retardation) for light with a wavelength of 550 nm.) Re(450) / Re(550)≦1.0 (2) 1.00≦Re(650) / Re(550) (3) (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.) When the "Re(450) / Re(550)" of a single retardation film exceeds 1.0, the light leakage on the short wavelength side of the optical laminate including the retardation film becomes large. The value of "Re(450) / Re(550)" is preferably 0.7 or more and 1.0 or less, more preferably 0.80 or more and 0.95 or less, even more preferably 0.80 or more and 0.92 or less, and particularly preferably 0.82 or more and 0.88 or less. The value of "Re(450) / Re(550)" can be arbitrarily adjusted by adjusting the mixing ratio of the polymerizable liquid crystal compound, the lamination angle of the multiple retardation films, and the retardation value.
[0061] The in-plane retardation value of the retardation film can be adjusted by the thickness of the retardation film. Since the in-plane retardation value is determined by the following formula (4), a desired in-plane retardation value (Re(λ)) can be obtained by adjusting Δn(λ) and the thickness d. The thickness of the retardation film is preferably 0.5 μm to 5 μm, more preferably 1 μm to 3 μm. The thickness of the retardation film can be measured by an interference thickness meter, a laser microscope, or a stylus thickness meter. Δn(λ) depends on the molecular structure of the polymerizable liquid crystal compound described later.
[0062] Re(λ)=d×Δn(λ) (4) (In the formula, Re(λ) represents an in-plane retardation value at a wavelength of λ nm, d represents a thickness, and Δn(λ) represents a birefringence at a wavelength of λ nm.) The positive C plate is not particularly limited as long as it has anisotropy in the thickness direction, but if it does not have tilt alignment or cholesteric alignment, it has the optical characteristics expressed by formula (5).
[0063] nx≒ny <nz (5) The in-plane retardation value Re(550) of the positive C plate at a wavelength of 550 nm is usually in the range of 0 to 10 nm, preferably in the range of 0 to 5 nm. The retardation value Rth(550) in the thickness direction at a wavelength of 550 nm is usually in the range of -170 nm or more and -10 nm or less, preferably in the range of -150 nm or more and -20 nm or less, more preferably in the range of -100 nm or more and -40 nm or less. If the retardation value in the thickness direction is in this range, the anti-reflection property from an oblique direction can be further improved.
[0064] The polymerizable liquid crystal compound contained in the retardation film forming composition means a liquid crystal compound having a polymerizable group, particularly a photopolymerizable group, and as the polymerizable liquid crystal compound, a conventionally known polymerizable liquid crystal compound can be used. The photopolymerizable group means a group that can participate in a polymerization reaction by a reactive species generated from a photopolymerization initiator, such as an active radical or an acid. Examples of the photopolymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The liquid crystal property may be a thermotropic liquid crystal or a lyotropic liquid crystal, but a thermotropic liquid crystal is preferred in terms of the ability to precisely control the film thickness. In addition, the phase order structure in the thermotropic liquid crystal may be a nematic liquid crystal or a smectic liquid crystal. The polymerizable liquid crystal compound may be either rod-shaped or discotic. The polymerizable liquid crystal compound may be used alone or in combination of two or more kinds.
[0065] As the polymerizable liquid crystal compound, from the viewpoint of expressing reverse wavelength dispersion, a liquid crystal having a T-shaped or H-shaped mesogenic structure that further has birefringence in a direction perpendicular to the molecular long axis direction is preferred, and from the viewpoint of obtaining stronger dispersion, a T-shaped liquid crystal is more preferred. Specific examples of the T-shaped liquid crystal structure include compounds represented by the following formula (I):
[0066] [ka]
[0067] In formula (I), Ar represents a divalent aromatic group which may have a substituent. The divalent aromatic group preferably contains at least one of a nitrogen atom, an oxygen atom, and a sulfur atom. When the divalent group Ar contains two or more aromatic groups, the two or more aromatic groups may be bonded to each other via a divalent bonding group such as a single bond, -CO-O-, or -O-.
[0068] G 1 and G 2 each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom.
[0069] L 1 , L 2 , B 1 and B. 2 each independently represents a single bond or a divalent linking group. k and l each independently represent an integer of 0 to 3, and satisfy the relationship of 1≦k+l. Here, when 2≦k+l, B 1 and B. 2 , G 1 and G 2 may be the same as or different from each other.
[0070] E 1 and E 2 each independently represents an alkanediyl group having 1 to 17 carbon atoms, in which a hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and -CH2- contained in the alkanediyl group may be substituted with -O-, -S-, or -COO-, and when there are a plurality of -O-, -S-, or -COO-, they are not adjacent to each other.1 and P 2 each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.
[0071] G 1 and G 2 are each independently preferably a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group. 1 and G 2 At least one of L is preferably a divalent alicyclic hydrocarbon group. 1 Or L 2 G binds to 1 and G 2 It is more preferable that at least one of the groups is a divalent alicyclic hydrocarbon group.
[0072] L 1 and L 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 O.C.O.R. a6 -, R a7 OC=OOR a8 -, -N=N-, -CR c =CR d - or -C≡C-, where R a1 ~R a8 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms; R c and R drepresents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 are each independently preferably a single bond, -OR a2-1 -, -CH2-, -CH2CH2-, -COOR a4-1 - or OCOR a6-1 -, where R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or OCO-.
[0073] B 1 and B. 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -, -R a11 COOR a12 -, -R a13 O.C.O.R. a14 - or R a15 OC=OOR a16 -, where R a9 ~R a16 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B. 2 are each independently preferably a single bond, -OR a10-1 -, -CH2-, -CH2CH2-, -COOR a12-1 - or OCOR a14-1 -, where R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. B 1 and B. 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or OCOCH2CH2-.
[0074] From the viewpoint of expressing reverse wavelength dispersion, k and l are preferably in the range of 2≦k+l≦6, preferably k+l=4, and more preferably k=2 and l=2. When k=2 and l=2, a symmetrical structure is obtained, which is preferable.
[0075] E 1 and E 2 are each independently preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms. P 1 Or P 2 Examples of the polymerizable group represented by the formula (I) include an epoxy group, a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among these, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred.
[0076] It is preferable that Ar has at least one selected from an aromatic hydrocarbon ring which may have a substituent, an aromatic heterocycle which may have a substituent, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring, and the like, and the benzene ring and the naphthalene ring are preferable. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenanthroline ring. Among them, it is preferable that Ar has a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is more preferable that Ar has a benzothiazole group. In addition, when Ar contains a nitrogen atom, it is preferable that the nitrogen atom has a π electron.
[0077] In formula (I), the total number of π electrons contained in the divalent aromatic group represented by Ar is N πis preferably 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Also, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.
[0078] Suitable examples of the aromatic group represented by Ar include the following groups:
[0079] [ka]
[0080] In formulae (Ar-1) to (Ar-23), * represents a linking portion, Z 0 , Z 1 and Z 2 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.
[0081] Q 1 , Q 2 and Q 3 are each independently -CR 2′ R 3′ -, -S-, -NH-, -NR 2′ represents -, -CO- or O-; R 2′ and R 3′ each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.
[0082] J 1 , and J 2 each independently represents a carbon atom or a nitrogen atom. Y 1 , Y 2 and Y 3each independently represents an optionally substituted aromatic hydrocarbon group or an optionally substituted aromatic heterocyclic group.
[0083] W 1 and W 2 each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom; and m represents an integer of 0 to 6. Y 1 , Y 2 and Y 3 Examples of the aromatic hydrocarbon group in the formula (I) include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group, of which a phenyl group and a naphthyl group are preferred, and a phenyl group is more preferred. Examples of the aromatic heterocyclic group in the formula (I) include aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one heteroatom, such as a nitrogen atom, an oxygen atom, or a sulfur atom, such as a furyl group, a pyrrolyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group, of which a furyl group, a thienyl group, a pyridinyl group, a thiazolyl group, and a benzothiazolyl group are preferred.
[0084] Y 1 , Y 2 and Y 3 may each independently be an optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.
[0085] Z 0 , Z 1 and Z 2 are each preferably independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms; Z 0 is more preferably a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group; Z 1 and Z 2 is more preferably a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group.
[0086] Q1 , Q 2 and Q 3 -NH-, -S-, -NR 2′ -, -O- are preferred, R 2′ is preferably a hydrogen atom, and among these, -S-, -O-, and -NH- are particularly preferable. Among the formulae (Ar-1) to (Ar-23), the formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.
[0087] In formulas (Ar-16) to (Ar-23), Y 1 is the nitrogen atom to which it is bonded and Z 0 and may form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include those mentioned above as aromatic heterocyclic rings that Ar may have, such as a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. This aromatic heterocyclic group may have a substituent. In addition, Y 1 is the nitrogen atom to which it is bonded and Z 0 In addition, it may be the above-mentioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group, for example, a benzofuran ring, a benzothiazole ring, a benzoxazole ring, etc.
[0088] Among the polymerizable liquid crystal compounds, compounds having a maximum absorption wavelength of 300 to 400 nm are preferred. When the polymerizable liquid crystal composition contains a photopolymerization initiator, the polymerization reaction and gelation of the polymerizable liquid crystal compound may proceed during long-term storage. However, if the polymerizable liquid crystal compound has a maximum absorption wavelength of 300 to 400 nm, even if the polymerizable liquid crystal composition is exposed to ultraviolet light during storage, the generation of reactive species from the photopolymerization initiator and the polymerization reaction and gelation of the polymerizable liquid crystal compound caused by the reactive species can be effectively suppressed. Therefore, it is advantageous in terms of long-term stability of the polymerizable liquid crystal composition, and the alignment property and thickness uniformity of the obtained retardation film can be improved. The maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using a UV-visible spectrophotometer in a solvent. The solvent is a solvent that can dissolve the polymerizable liquid crystal compound, and examples thereof include chloroform and the like.
[0089] An example of the discotic polymerizable liquid crystal compound is a compound containing a group represented by formula (W) (hereinafter, also referred to as "polymerizable liquid crystal compound (W)").
[0090] [ka]
[0091] [In formula (W), R 40 represents the following formulas (W-1) to (W-5).
[0092] [ka]
[0093] [In formulas (W-1) to (W-5), X 40 and Z 40 each independently represents an alkanediyl group having 1 to 12 carbon atoms, and a hydrogen atom contained in the alkanediyl group may be substituted with an alkoxy group having 1 to 5 carbon atoms, and a hydrogen atom contained in the alkoxy group may be substituted with a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced with -O- or -CO-. m2 represents an integer.] Examples of the rod-shaped polymerizable liquid crystal compound include compounds represented by formula (II), formula (III), formula (IV), formula (V), formula (VI) or formula (VII).
[0094] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (II) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (III) P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (IV) P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (V) P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (VI) P11-B11-E11-B12-A11-B13-A12-F11 (VII) [In formulas (II) to (VII), A11 to A14 each independently represent a divalent alicyclic hydrocarbon group or a divalent aromatic hydrocarbon group. A hydrogen atom contained in the divalent alicyclic hydrocarbon group and the divalent aromatic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a cyano group, or a nitro group, and a hydrogen atom contained in the alkyl group having 1 to 6 carbon atoms and the alkoxy group having 1 to 6 carbon atoms may be substituted with a fluorine atom.
[0095] B11 and B17 each independently represent -O-, -S-, -CO-O-, -O-CO-, -O-CO-O-, or -CO-NR 16 -, -NR 16 R represents -CO-, -CO-, -CS-, or a single bond. 16 represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms.
[0096] B12 to B16 each independently represent -C≡C-, -CH=CH-, -CH2-CH2-, -O-, -S-, -C(=O)-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -CH=N-, -N=CH-, -N=N-, -C(=O)-NR 16 -, -NR 16 It represents -C(=O)-, -OCH2-, -OCF2-, -CH2O-, -CF2O-, -CH=CH-C(=O)-O-, -OC(=O)-CH=CH- or a single bond.
[0097] E11 and E12 each independently represent an alkanediyl group having 1 to 12 carbon atoms, and a hydrogen atom contained in the alkanediyl group may be substituted with an alkoxy group having 1 to 5 carbon atoms, and a hydrogen atom contained in the alkoxy group may be substituted with a halogen atom. In addition, -CH2- constituting the alkanediyl group may be replaced with -O- or -CO-.
[0098] F11 represents a hydrogen atom, an alkyl group having 1 to 13 carbon atoms, an alkoxy group having 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxy group, a methylol group, a formyl group, a sulfo group (-SO3H), a carboxy group, an alkoxycarbonyl group having 1 to 10 carbon atoms, or a halogen atom, and -CH2- constituting the alkyl group and the alkoxy group may be replaced by -O-.
[0099] P11 and P12 each independently represent a polymerizable group.] The content of the polymerizable liquid crystal compound in the retardation film forming composition is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, more preferably 85 to 98 parts by mass, and even more preferably 90 to 95 parts by mass, based on 100 parts by mass of the solid content of the retardation film forming composition. If the content of the polymerizable liquid crystal compound is within the above range, it is advantageous from the viewpoint of the alignment of the obtained retardation film. In this specification, the solid content of the polymerizable liquid crystal composition means all components excluding volatile components such as organic solvents from the polymerizable liquid crystal composition.
[0100] (3-2) Composition for forming retardation film As described above, the retardation film forming composition contains a polymerizable liquid crystal compound. The retardation film forming composition may further contain reactive additives such as a solvent, a leveling agent, a polymerization initiator, a photosensitizer, a polymerization inhibitor, a crosslinking agent, and an adhesive agent, and it is preferable to contain a solvent and a leveling agent from the viewpoint of processability.
[0101] The retardation film forming composition may contain a solvent. Generally, the polymerizable liquid crystal compound has a high viscosity, so that the retardation film forming composition dissolved in a solvent is easy to apply, and as a result, the retardation film is often easy to form. The solvent is preferably one that can completely dissolve the polymerizable liquid crystal compound, and is preferably a solvent that is inactive to the polymerization reaction of the polymerizable liquid crystal compound.
[0102] Examples of the solvent include alcohol solvents such as methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, ethylene glycol methyl ether, ethylene glycol butyl ether, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone or propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene, and nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; chlorine-containing solvents such as chloroform and chlorobenzene; and amide solvents such as dimethylacetamide, dimethylformamide, N-methyl-2-pyrrolidone, and 1,3-dimethyl-2-imidazolidinone. These solvents may be used alone or in combination of two or more.
[0103] The content of the solvent is preferably 50 to 98% by mass based on the total amount of the composition for forming a retardation film. In other words, the content of the solid content in the composition for forming a retardation film is preferably 2 to 50% by mass, more preferably 5 to 30% by mass. When the content of the solid content is 50% by mass or less, the viscosity of the composition for forming a retardation film is low, and the thickness of the retardation film becomes approximately uniform, so that the retardation film tends to be less prone to unevenness. In addition, the content of the solid content can be determined in consideration of the thickness of the retardation film to be produced.
[0104] The retardation film forming composition may contain a leveling agent. The leveling agent is an additive that adjusts the fluidity of the composition and makes the film obtained by applying the composition flatter, and examples of the leveling agent include organic modified silicone-based, polyacrylate-based and perfluoroalkyl-based leveling agents. Among them, when horizontal alignment is performed, polyacrylate-based and perfluoroalkyl-based leveling agents are preferred, and when vertical alignment is performed, organic modified silicone-based and perfluoroalkyl-based leveling agents are preferred.
[0105] When the composition for forming a retardation film contains a leveling agent, the content is preferably 0.01 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the polymerizable liquid crystal compound is easily aligned horizontally, and the obtained retardation film tends to be smoother. When the content of the leveling agent relative to the polymerizable liquid crystal compound exceeds the above range, the obtained retardation film tends to be easily uneven. The composition for forming a retardation film may contain two or more kinds of leveling agents.
[0106] The retardation film-forming composition may contain a polymerization initiator. The polymerization initiator is a compound capable of initiating a polymerization reaction of a polymerizable liquid crystal compound, etc. As the polymerization initiator, a photopolymerization initiator that generates active radicals by the action of light is preferable from the viewpoint of not depending on the phase state of the thermotropic liquid crystal.
[0107] The photopolymerization initiator can be any known photopolymerization initiator as long as it is a compound capable of initiating the polymerization reaction of the polymerizable liquid crystal compound.Specific examples of the photopolymerization initiator include photopolymerization initiators capable of generating active radicals or acids by the action of light, and among these, photopolymerization initiators that generate radicals by the action of light are preferred.The photopolymerization initiators can be used alone or in combination of two or more kinds.
[0108] As the photopolymerization initiator, a known photopolymerization initiator can be used. For example, as a photopolymerization initiator that generates an active radical, a self-cleavage type benzoin compound, acetophenone compound, hydroxyacetophenone compound, α-aminoacetophenone compound, oxime ester compound, acylphosphine oxide compound, azo compound, etc. can be used, and a hydrogen abstraction type benzophenone compound, alkylphenone compound, benzoin ether compound, benzyl ketal compound, dibenzosuberone compound, anthraquinone compound, xanthone compound, thioxanthone compound, halogenoacetophenone compound, dialkoxyacetophenone compound, halogenobisimidazole compound, halogenotriazine compound, triazine compound, etc. can be used. As a photopolymerization initiator that generates an acid, an iodonium salt and a sulfonium salt can be used. From the viewpoint of excellent reaction efficiency at low temperatures, self-cleavage type photopolymerization initiators are preferred, and in particular, acetophenone-based compounds, hydroxyacetophenone-based compounds, α-aminoacetophenone-based compounds, and oxime ester-based compounds are preferred.
[0109] The content of the polymerization initiator in the retardation film-forming composition can be appropriately adjusted depending on the type and amount of the polymerizable liquid crystal compound, but is usually 0.1 to 30 parts by mass, preferably 0.5 to 10 parts by mass, and more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the polymerization initiator is within the above range, polymerization can be performed without disturbing the alignment of the polymerizable liquid crystal compound.
[0110] The retardation film forming composition may contain a sensitizer. The sensitizer is preferably a photosensitizer. Examples of the sensitizer include xanthone compounds such as xanthone and thioxanthone (e.g., 2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.); anthracene compounds such as anthracene and an alkoxy group-containing anthracene (e.g., dibutoxyanthracene, etc.); phenothiazine, rubrene, etc.
[0111] When the retardation film-forming composition contains a sensitizer, the polymerization reaction of the polymerizable liquid crystal compound contained in the retardation film-forming composition can be further promoted. The amount of the sensitizer used is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound.
[0112] In order to stably proceed with the polymerization reaction, the retardation film-forming composition may contain an antioxidant, which can control the degree of progress of the polymerization reaction of the polymerizable liquid crystal compound.
[0113] The antioxidant may be, for example, a primary antioxidant selected from a phenol-based antioxidant, an amine-based antioxidant, a quinone-based antioxidant, or a nitroso-based antioxidant, or a secondary antioxidant selected from a phosphorus-based antioxidant and a sulfur-based antioxidant.
[0114] When the retardation film forming composition contains an antioxidant, the content of the antioxidant is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and further preferably 0.5 to 8 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. The antioxidants can be used alone or in combination of two or more kinds. When the content of the antioxidant is within the above range, polymerization can be performed without disturbing the alignment of the polymerizable liquid crystal compound.
[0115] The retardation film forming composition may contain a reactive additive. The reactive additive preferably has a carbon-carbon unsaturated bond, an active hydrogen reactive group, or a thiol group in its molecule. The "active hydrogen reactive group" here means a group reactive to a group having active hydrogen such as a carboxyl group (-COOH), a hydroxyl group (-OH), or an amino group (-NH2), and representative examples thereof include a glycidyl group, an oxazoline group, a carbodiimide group, an aziridine group, an imide group, an isocyanate group, a thioisocyanate group, and a maleic anhydride group. The number of reactive groups possessed by the reactive additive is usually 1 to 20, and preferably 1 to 10.
[0116] (3-3) Base material The above-mentioned substrate for forming the retardation film includes glass substrate and film substrate, and film substrate is preferred, and long roll-shaped film is more preferred in terms of continuous production.The resin constituting the film substrate includes, for example, linear polyolefin such as polyethylene and polypropylene; cyclic olefin resin; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid ester; polyacrylic acid ester; cellulose ester such as triacetyl cellulose, diacetyl cellulose and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide and polyphenylene oxide; and the like.Among them, from the viewpoint of transparency when used for optical film applications, a film substrate selected from any of triacetyl cellulose, cyclic olefin resin, polymethacrylic acid ester, and polyethylene terephthalate is more preferred.
[0117] Examples of commercially available cellulose ester substrates include "FUJITAC FILM" (manufactured by Fuji Photo Film Co., Ltd.); "KC8UX2M", "KC8UY" and "KC4UY" (all manufactured by Konica Minolta Opto Co., Ltd.). Examples of commercially available cyclic olefin resins include "Topas" (registered trademark) (manufactured by Ticona (Germany)), "ARTON" (registered trademark) (manufactured by JSR Corporation), "ZEONOR" (registered trademark), "ZEONEX" (registered trademark) (all manufactured by Zeon Corporation) and "Apel" (registered trademark) (manufactured by Mitsui Chemicals, Inc.). Such cyclic olefin resins can be formed into a film by known means such as a solvent casting method or a melt extrusion method to form a substrate. Commercially available cyclic olefin resin substrates can also be used. Commercially available cyclic olefin resin substrates include "S-Cina" (registered trademark), "SCA40" (registered trademark) (both manufactured by Sekisui Chemical Co., Ltd.), "ZEONORFILM" (registered trademark) (manufactured by Optes Co., Ltd.), and "ARTONFILM" (registered trademark) (manufactured by JSR Corporation).
[0118] The thickness of the substrate is preferably thin enough to be practically handled, but if it is too thin, the strength decreases and the processability tends to be poor. The thickness of the substrate is usually 5 μm to 300 μm, preferably 10 μm to 200 μm, and more preferably 10 to 50 μm. In addition, by peeling off the substrate and transferring the retardation film, a further thinning effect can be obtained.
[0119] (3-4) Alignment film In this specification, the alignment film has an alignment regulating force for aligning a polymerizable liquid crystal compound in a desired direction.
[0120] The alignment film facilitates the liquid crystal alignment of the polymerizable liquid crystal compound. The state of liquid crystal alignment, such as horizontal alignment, vertical alignment, hybrid alignment, and tilt alignment, varies depending on the properties of the alignment film and the polymerizable liquid crystal compound, and the combination can be selected arbitrarily. For example, if the alignment film is a material that exerts horizontal alignment as an alignment control force, the polymerizable liquid crystal compound can form a horizontal alignment or a hybrid alignment, and if the alignment film is a material that exerts vertical alignment, the polymerizable liquid crystal compound can form a vertical alignment or a tilt alignment. The expressions horizontal, vertical, and the like refer to the direction of the optical axis of the aligned polymerizable liquid crystal compound when the retardation film plane is used as a reference. For example, vertical alignment means that the optical axis of the aligned polymerizable liquid crystal compound is in a direction perpendicular to the retardation film plane. The term "vertical" here means 90°±20° relative to the retardation film plane.
[0121] When the alignment film is made of an alignment polymer, the alignment regulating force can be arbitrarily adjusted by the surface state or rubbing conditions, and when it is made of a photoalignment polymer, the alignment regulating force can be arbitrarily adjusted by the polarized light irradiation conditions, etc. In addition, the liquid crystal alignment can be controlled by selecting the physical properties, such as the surface tension and liquid crystallinity, of the polymerizable liquid crystal compound.
[0122] The alignment film formed between the substrate and the retardation film is preferably insoluble in the solvent used when forming the retardation film on the alignment film, and is heat-resistant in the heat treatment for removing the solvent and for aligning the liquid crystal. The alignment film may be an alignment film made of an orienting polymer, a photoalignment film, a groove alignment film, or a stretched film stretched in the alignment direction. When applied to a long rolled film, a photoalignment film is preferred because the alignment direction can be easily controlled.
[0123] The thickness of the alignment film is usually in the range of 10 nm to 5000 nm, preferably in the range of 10 nm to 1000 nm, and more preferably in the range of 30 to 300 nm. Examples of the alignment polymer used in the rubbed alignment film include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and their hydrolyzates such as polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among these, polyvinyl alcohol is preferred. These alignment polymers may be used alone or in combination of two or more.
[0124] An example of a rubbing method is to bring an oriented polymer film formed on the surface of a substrate by applying an oriented polymer composition to the substrate and annealing the composition into contact with a rotating rubbing roll wrapped with a rubbing cloth.
[0125] The photo-alignment film is made of a polymer, oligomer, or monomer having a photoreactive group. The photo-alignment film can obtain an alignment control force by irradiating it with polarized light. The photo-alignment film is more preferable in that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.
[0126] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it is a group that generates a photoreaction that is the origin of liquid crystal alignment ability, such as molecular alignment induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, which occurs by irradiation with light. Among the photoreactive groups, those that cause a dimerization reaction or a photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group that can generate the above-mentioned reaction, those having an unsaturated bond, particularly a double bond, are preferred, and groups having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) are more preferred.
[0127] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazole groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. From the viewpoint of easy control of reactivity and expression of alignment control force during photoalignment, chalcone groups and cinnamoyl groups are preferred. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, and formazan groups, and groups having azoxybenzene as a basic structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.
[0128] The polarized light may be irradiated directly from the film surface or from the substrate side and then transmitted. It is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is particularly preferable. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, and ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferable. These lamps are preferable because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. The light from the light source can be irradiated through an appropriate polarizer to irradiate the polarized light. As such a polarizer, a polarizing filter, a polarizing prism such as Glan-Thompson or Glan-Taylor, or a wire grid type polarizer can be used.
[0129] (4) Lamination layer (4-1) First lamination layer The first bonding layer 30a is a pressure-sensitive adhesive layer or an adhesive layer, and is preferably a pressure-sensitive adhesive layer. The first bonding layer 30a bonds the polarizer 101 and the retardation plate 20. That is, the first bonding layer 30a is in direct contact with the polarizer 101 and the retardation plate 20.
[0130] The thickness of the first bonding layer 30a is, for example, 0.5 μm or more and 25 μm or less. The upper limit of the above range is preferably 20 μm, and more preferably 18 μm. The lower limit of the above range is preferably 1 μm, and more preferably 3 μm.
[0131] When the thickness of the first bonding layer 30a is within the above numerical range, the thickness of the first bonding layer 30a is relatively thin. Since the distance between the image display element 40 and the polarizer 101 is short, it is easy to prevent the end of the polarizer 101 from swelling. The thickness of the first bonding layer 30a may be, for example, more than 10 μm, but is preferably 10 μm or less, particularly 7 μm or less, in terms of further reducing the thickness.
[0132] The first bonding layer 30a may have selective light absorption properties. That is, the first bonding layer 30a may contain a light absorbing agent. The light absorbing agent is preferably an ultraviolet absorbing agent. (4-2) Second lamination layer The second attachment layer 30b is a pressure-sensitive adhesive layer or an adhesive layer, and is preferably a pressure-sensitive adhesive layer. The second attachment layer 30b bonds the optical laminate 1 to, for example, the image display element 40 or the like.
[0133] The thickness of the second bonding layer 30b is, for example, 5 μm or more and 30 μm or less. The upper limit of the above range is preferably 25 μm, and more preferably 20 μm. The lower limit of the above range is preferably 10 μm.
[0134] The second bonding layer 30b may have selective light absorption properties. That is, the second bonding layer 30b may contain a light absorbing agent. The light absorbing agent is preferably an ultraviolet absorbing agent. (4-3) Third lamination layer The third bonding layer 30c is a pressure sensitive adhesive layer or an adhesive layer, and is preferably an adhesive layer. More preferably, it is an adhesive layer obtained by curing an active energy ray curable adhesive, and even more preferably, it is an adhesive layer obtained by curing an ultraviolet ray curable adhesive. When the third bonding layer 30c is an adhesive layer, it is possible to suppress the occurrence of wrinkles in the liquid crystal cured layer when the circular polarizer is folded or folded. The third bonding layer 30c bonds the first liquid crystal cured layer 201 and the second liquid crystal cured layer 202.
[0135] The retardation plate 20 may have a selective light absorption property. For example, the third bonding layer 30c may contain a light absorbing agent. The light absorbing agent is preferably an ultraviolet absorbing agent. The thickness of the third bonding layer 30c is, for example, 0.5 μm or more and 4.5 μm or less. The upper limit of the above range is preferably 3.5 μm, and more preferably 2.5 μm. The lower limit of the above range is preferably 1 μm, and more preferably 1.5 μm.
[0136] When the thickness of the third bonding layer 30c is 0.5 μm or more, it is possible to improve the adhesion to the first cured liquid crystal layer 201 and the second cured liquid crystal layer 202. When the thickness of the third bonding layer 30c is 4.5 μm or less, it is possible to easily suppress the end portion of the polarizer 101 from swelling.
[0137] (4-4) Adhesive layer As the adhesive composition forming the adhesive layer, a conventionally known adhesive composition having excellent optical transparency can be used without any particular limitation, and for example, an adhesive composition having a base polymer such as an acrylic resin, a urethane resin, a silicone resin, or a polyvinyl ether resin can be used. In addition, it may be an active energy ray curable adhesive composition, a heat curable adhesive composition, or the like. Among these, an adhesive composition having an acrylic resin as a base polymer, which is excellent in transparency, adhesive strength, removability, weather resistance, heat resistance, etc., is preferable. The adhesive composition may further contain a crosslinking agent, a silane compound, an antistatic agent, etc.
[0138] [(Meth)acrylic resin] The (meth)acrylic resin contained in the pressure-sensitive adhesive composition is preferably a polymer (hereinafter also referred to as a "(meth)acrylic acid ester polymer") having as its main component (e.g., containing 50 parts by mass or more per 100 parts by mass of the structural unit of the (meth)acrylic resin) a structural unit derived from a (meth)acrylic acid alkyl ester represented by the following formula (Ia) (hereinafter also referred to as "structural unit (Ia)").
[0139] In this specification, the (meth)acrylic resin means either an acrylic resin or a methacrylic resin, and the "(meth)" in (meth)acrylate has the same meaning.
[0140] [ka]
[0141] [In the formula, R 10 represents a hydrogen atom or a methyl group, and R 20represents an alkyl group having 1 to 20 carbon atoms, the alkyl group may have any of a linear, branched, or cyclic structure, and a hydrogen atom of the alkyl group may be replaced by an alkoxy group having 1 to 10 carbon atoms.] Examples of the (meth)acrylic acid ester represented by formula (Ia) include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, i-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n Examples of the alkyl acrylates containing an alkoxy group include 2-methoxyethyl (meth)acrylate, ethoxymethyl (meth)acrylate, etc. ...
[0142] The (meth)acrylic acid ester polymer may contain a structural unit derived from a monomer other than the structural unit (Ia). The structural unit derived from the other monomer may be one type or two or more types. Examples of the other monomer that the (meth)acrylic acid ester polymer may contain include a monomer having a polar functional group, a monomer having an aromatic group, and an acrylamide monomer.
[0143] The monomer having a polar functional group may be a (meth)acrylate having a polar functional group, such as a hydroxy group, a carboxy group, an amino group substituted with an alkyl group having 1 to 6 carbon atoms or an unsubstituted amino group, or a heterocyclic group such as an epoxy group.
[0144] The content of the structural units derived from the monomer having a polar functional group in the (meth)acrylic acid ester polymer is preferably 10 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, even more preferably 0.5 parts by mass or more and 5 parts by mass or less, and particularly preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of all structural units of the (meth)acrylic acid ester polymer.
[0145] Examples of monomers having an aromatic group include (meth)acrylic acid esters having one (meth)acryloyl group and one or more aromatic rings (e.g., benzene ring, naphthalene ring, etc.) in the molecule and having a phenyl group, a phenoxyethyl group, or a benzyl group. By including these structural units, it is possible to suppress the white spot phenomenon that occurs in polarizing plates in high temperature and high humidity environments.
[0146] The content of structural units derived from monomers having an aromatic group in the (meth)acrylic acid ester polymer is preferably 20 parts by mass or less, more preferably 4 parts by mass or more and 20 parts by mass or less, and even more preferably 4 parts by mass or more and 15 parts by mass or less, relative to 100 parts by mass of all structural units of the (meth)acrylic acid ester polymer.
[0147] Examples of the acrylamide monomer include N-(methoxymethyl)acrylamide, N-(ethoxymethyl)acrylamide, N-(propoxymethyl)acrylamide, N-(butoxymethyl)acrylamide, N-(2-methylpropoxymethyl)acrylamide, etc. By including these structural units, it is possible to suppress the bleeding out of additives such as antistatic agents, which will be described later.
[0148] Furthermore, structural units derived from monomers other than the structural unit (Ia) may include structural units derived from styrene-based monomers, structural units derived from vinyl-based monomers, structural units derived from monomers having multiple (meth)acryloyl groups in the molecule, and the like.
[0149] The weight average molecular weight (hereinafter, simply referred to as "Mw") of the (meth)acrylic resin (1) is preferably 500,000 to 2,500,000. When the weight average molecular weight is 500,000 or more, the durability of the first pressure-sensitive adhesive layer in a high-temperature and high-humidity environment can be improved. When the weight average molecular weight is 2,500,000 or less, the operability during application of a coating liquid containing the pressure-sensitive adhesive composition is improved. The molecular weight distribution (Mw / Mn), which is expressed as the ratio of the weight average molecular weight (Mw) to the number average molecular weight (hereinafter, simply referred to as "Mn"), is usually 2 to 10. In this specification, the "weight average molecular weight" and the "number average molecular weight" are polystyrene-equivalent values measured by gel permeation chromatography (GPC).
[0150] When the (meth)acrylic resin is dissolved in ethyl acetate to prepare a solution having a concentration of 20% by mass, the viscosity at 25° C. is preferably 20 Pa·s or less, and more preferably 0.1 to 15 Pa·s. When the viscosity of the (meth)acrylic resin at 25° C. is within the above range, it contributes to improving the durability and reworkability of a polarizing plate including a pressure-sensitive adhesive layer formed from the resin. The viscosity can be measured by a Brookfield viscometer.
[0151] The glass transition temperature (Tg) of the (meth)acrylic resin is, for example, −60 to 20° C., preferably −50 to 15° C., more preferably −45 to 10° C., and further preferably −40 to 0° C. The glass transition temperature can be measured by a differential scanning calorimeter (DSC).
[0152] The (meth)acrylic resin may contain two or more kinds of (meth)acrylic acid ester polymers. Examples of such (meth)acrylic acid ester polymers include (meth)acrylic acid ester polymers having a relatively low molecular weight, such as those mainly composed of the structural unit (Ia) derived from the (meth)acrylic acid ester and having a weight average molecular weight in the range of 50,000 to 300,000.
[0153] The (meth)acrylic resin can be usually produced by a known polymerization method such as a solution polymerization method, a bulk polymerization method, a suspension polymerization method, or an emulsion polymerization method. In the production of the (meth)acrylic resin, the polymerization is usually carried out in the presence of a polymerization initiator. The amount of the polymerization initiator used is usually 0.001 to 5 parts by mass with respect to 100 parts by mass of the total of all the monomers constituting the (meth)acrylic resin. The (meth)acrylic resin can also be produced by a method of polymerization using active energy rays such as ultraviolet rays.
[0154] [Crosslinking agent] The pressure-sensitive adhesive composition preferably contains a crosslinking agent. Examples of the crosslinking agent include conventional crosslinking agents (e.g., isocyanate compounds, epoxy compounds, aziridine compounds, metal chelate compounds, peroxides, etc.), and from the viewpoints of the pot life of the pressure-sensitive adhesive composition, crosslinking speed, and durability of the polarizing plate, it is particularly preferable to use an isocyanate compound.
[0155] The isocyanate compound is a compound having at least two isocyanato groups (-NCO) in the molecule. Specific examples include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, and triphenylmethane triisocyanate. In addition, adducts obtained by reacting these isocyanate compounds with polyols such as glycerol and trimethylolpropane, and dimers and trimers of these isocyanate compounds are also included. Two or more types of isocyanate compounds may be combined.
[0156] The proportion of the crosslinking agent is, for example, 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the (meth)acrylic resin.
[0157] [Silane compounds] The pressure-sensitive adhesive composition may further contain a silane compound. Examples of the silane compound include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylethoxydimethylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.
[0158] The silane compound may also contain an oligomer derived from the above silane compound. The content of the silane compound in the pressure-sensitive adhesive composition is usually 0.01 to 10 parts by mass, and preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin. When the content of the silane compound is 0.01 part by mass or more, the adhesion between the pressure-sensitive adhesive layer and the adherend tends to be improved, and when the content is 10 parts by mass or less, bleeding out of the silane compound from the pressure-sensitive adhesive layer tends to be suppressed.
[0159] [Antistatic agent] The pressure-sensitive adhesive composition may further contain an antistatic agent. Examples of the antistatic agent include known ones, and ionic antistatic agents are preferred. Examples of the cationic component constituting the ionic antistatic agent include organic cations and inorganic cations. Examples of the organic cation include pyridinium cation, imidazolium cation, ammonium cation, sulfonium cation, phosphonium cation, etc. Examples of the inorganic cation include alkali metal cations such as lithium cation, potassium cation, sodium cation, and cesium cation, and alkaline earth metal cations such as magnesium cation and calcium cation. Examples of the anionic component constituting the ionic antistatic agent include inorganic anions and organic anions, but an anionic component containing a fluorine atom is preferred in terms of excellent antistatic performance. Examples of the anionic component containing a fluorine atom include hexafluorophosphate anion (PF6 - ), bis(trifluoromethanesulfonyl)imide anion [(CF3SO2)2N - ], bis(fluorosulfonyl)imide anion [(FSO2)2N - ] anion, etc.
[0160] In view of excellent stability over time of the antistatic performance of the pressure-sensitive adhesive composition, an ionic antistatic agent that is solid at room temperature is preferred. The content of the antistatic agent is, for example, 0.01 to 20 parts by mass, preferably 0.1 to 10 parts by mass, and more preferably 1 to 7 parts by mass, relative to 100 parts by mass of the (meth)acrylic resin.
[0161] The adhesive composition may contain one or more additives such as an ultraviolet absorber, a solvent, a crosslinking catalyst, a tackifier resin, a plasticizer, etc. It is also useful to blend an ultraviolet curable compound into the adhesive composition, form an adhesive layer, and then irradiate the adhesive with ultraviolet light to cure the adhesive layer, thereby forming a harder adhesive layer.
[0162] The pressure-sensitive adhesive layer can be formed, for example, by dissolving or dispersing the pressure-sensitive adhesive composition in a solvent to prepare a solvent-containing pressure-sensitive adhesive composition, which is then applied to the surface of the layer on which the pressure-sensitive adhesive layer is to be formed, and drying.
[0163] The thickness of the pressure-sensitive adhesive layer is usually 0.1 to 30 μm, preferably 3 to 30 μm, and more preferably 5 to 25 μm. (4-5) Adhesive layer The adhesive layer may be formed from an adhesive composition.
[0164] Examples of the adhesive composition include an aqueous adhesive composition, and a curable adhesive composition that is cured by heating or irradiation with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. Examples of the aqueous adhesive composition include a composition in which a polyvinyl alcohol resin or a urethane resin is dissolved in water as the main component, and a composition in which a polyvinyl alcohol resin or a urethane resin is dispersed in water as the main component. The aqueous adhesive composition may further contain a curable component or a crosslinking agent such as a polyaldehyde, a melamine compound, a zirconia compound, a zinc compound, a glyoxal compound, or a water-soluble epoxy resin. Examples of the aqueous adhesive composition include the adhesive composition described in JP 2010-191389 A, the adhesive composition described in JP 2011-107686 A, the composition described in JP 2020-172088 A, and the composition described in JP 2005-208456 A.
[0165] The curable adhesive composition is preferably an active energy ray curable adhesive composition that contains a curable (polymerizable) compound as a main component and is cured by irradiation with active energy rays. Examples of the active energy ray curable adhesive composition include a cationic polymerization type adhesive composition that contains a cationic polymerizable compound as a curable compound, a radical polymerization type adhesive composition that contains a radical polymerizable compound as a curable compound, and a hybrid type adhesive composition that contains both a cationic polymerizable compound and a radical polymerizable compound as a curable compound.
[0166] The cationically polymerizable compound is a compound or oligomer that undergoes a cationic polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays, or when heated. Specific examples of the cationically polymerizable compound include epoxy compounds, oxetane compounds, and vinyl compounds.
[0167] Examples of epoxy compounds include alicyclic epoxy compounds such as 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (compounds having one or more epoxy groups bonded to an alicyclic ring in the molecule); aromatic epoxy compounds such as diglycidyl ether of bisphenol A (compounds having an aromatic ring and an epoxy group in the molecule); and aliphatic epoxy compounds such as 2-ethylhexyl glycidyl ether and 1,4-butanediol diglycidyl ether (compounds having at least one oxirane ring bonded to an aliphatic carbon atom in the molecule).
[0168] Examples of the oxetane compound include compounds having one or more oxetane rings in the molecule, such as 3-ethyl-3-{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane.
[0169] The cationic polymerization adhesive composition preferably contains a cationic polymerization initiator. The cationic polymerization initiator may be a thermal cationic polymerization initiator or a photo-induced cationic polymerization initiator. Examples of the cationic polymerization initiator include aromatic diazonium salts such as benzenediazonium hexafluoroantimonate; aromatic iodonium salts such as diphenyliodonium tetrakis(pentafluorophenyl)borate; aromatic sulfonium salts such as triphenylsulfonium hexafluorophosphate; and iron-arene complexes such as xylene-cyclopentadienyl iron(II) hexafluoroantimonate. The content of the cationic polymerization initiator is usually 0.1 to 10 parts by mass relative to 100 parts by mass of the cationic polymerizable compound. Two or more kinds of cationic polymerization initiators may be included.
[0170] Examples of cationic polymerization adhesive compositions include the cationic polymerizable compositions described in JP 2016-126345 A, WO 2019 / 10315 A, and JP 2021-113969 A.
[0171] The radical polymerizable compound is a compound or oligomer that undergoes a radical polymerization reaction and hardens when exposed to active energy rays such as ultraviolet light, visible light, electron beams, and X-rays or when heated, and specifically includes a compound having an ethylenically unsaturated bond. Examples of the compound having an ethylenically unsaturated bond include a (meth)acrylic compound having one or more (meth)acryloyl groups in the molecule, and a vinyl compound having one or more vinyl groups in the molecule.
[0172] Examples of the (meth)acrylic compound include (meth)acrylate monomers having at least one (meth)acryloyloxy group in the molecule, (meth)acrylamide monomers, and (meth)acryloyl group-containing compounds such as (meth)acrylic oligomers obtained by reacting two or more functional group-containing compounds and having at least two (meth)acryloyl groups in the molecule. In this specification, (meth)acryloyl means either acryloyl or methacryloyl.
[0173] The radical polymerization adhesive composition preferably contains a radical polymerization initiator. The radical polymerization initiator may be a thermal radical polymerization initiator or a photoradical polymerization initiator. Examples of the radical polymerization initiator include acetophenone-based initiators such as acetophenone and 3-methylacetophenone; benzophenone-based initiators such as benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; thioxanthone-based initiators such as 4-isopropylthioxanthone; xanthone, fluorenone, and the like. The content of the radical polymerization initiator is usually 0.1 to 10 parts by mass relative to 100 parts by mass of the radical polymerizable compound. Two or more types of radical polymerization initiators may be included.
[0174] Examples of radical polymerization adhesive compositions include the radical polymerizable compositions described in JP 2016-126345 A, JP 2016-153474 A, and WO 2017 / 183335 A.
[0175] The active energy ray-curable adhesive composition may contain additives such as an ion trapping agent, an antioxidant, a chain transfer agent, a tackifier, a thermoplastic resin, a filler, a flow adjuster, a plasticizer, an antifoaming agent, an antistatic agent, a leveling agent, and a solvent, as necessary.
[0176] The bonding of two layers with an adhesive layer can be carried out by coating at least one of the bonding surfaces of each of the two layers with an adhesive composition, overlapping the two layers with the coating layer of the adhesive composition therebetween, pressing the layers together from above and below using a lamination roll or the like, and then drying the adhesive layer, curing it by irradiating it with active energy rays, or curing it by heating.
[0177] Before forming the coating layer of the adhesive layer, at least one of the bonding surfaces of the two layers may be subjected to an adhesion enhancing treatment such as saponification treatment, corona treatment, plasma treatment, primer treatment, anchor coating treatment, etc.
[0178] To form a coating layer of the adhesive composition, various coating methods can be used, such as a die coater, a comma coater, a gravure coater, a wire bar coater, or a doctor blade coater.
[0179] The light irradiation intensity when irradiating with active energy rays is determined depending on the composition of the active energy ray-curable adhesive composition and is not particularly limited, but is preferably 10 mW / cm 2 More than 1,000mW / cm 2 The irradiation intensity is preferably an intensity in a wavelength region effective for activating a photocationic polymerization initiator or a photoradical polymerization initiator. Irradiation is performed once or multiple times with such a light irradiation intensity, and the integrated light amount is 10 mJ / cm or less. 2More preferably, it is 100 mJ / cm or more. 2 More than 1,000mJ / cm 2 It is more preferable to set it as follows:
[0180] The light source used to polymerize and cure the active energy ray-curable adhesive composition is not particularly limited, but examples include low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, xenon lamps, halogen lamps, chemical lamps, black light lamps, microwave excited mercury lamps, and metal halide lamps.
[0181] The thickness of the adhesive layer formed from the aqueous adhesive composition may be, for example, 5 μm or less, preferably 1 μm or less, and more preferably 0.5 μm or less, and may be 0.01 μm or more, and preferably 0.05 μm or more.
[0182] The thickness of the adhesive layer formed from the active energy ray-curable adhesive composition may be, for example, 10 μm or less, preferably 5 μm or less, and more preferably 3 μm or less, and may be 0.1 μm or more, preferably 0.5 μm or more, and more preferably 1 μm or more.
[0183] (5) Surface protection film The surface protective film is provided on the surface of the polarizer 101 for the purpose of preventing the surface of the polarizer 101 from being soiled or scratched. The surface protective film may be a resin film for surface protective film on which the above-mentioned pressure-sensitive adhesive layer is formed, or may be a self-adhesive film alone. The thickness of the surface protective film may be, for example, 30 μm or more and 200 μm or less, preferably 30 μm or more and 150 μm or less, and more preferably 30 μm or more and 120 μm or less.
[0184] After the optical laminate 1 is bonded to an image display element such as a liquid crystal cell or other optical components, the surface protection film is peeled off and removed together with the adhesive layer contained in the surface protection film, or the resin film for the surface protection film is peeled off and removed while leaving the adhesive layer on the surface of the polarizer.
[0185] The surface protection film may contain an antistatic agent. The antistatic agent may be contained in, for example, the adhesive layer. Instead of or in addition to containing an antistatic agent in the adhesive layer, an antistatic layer containing an antistatic agent may be provided on the surface of the resin film for surface protection film opposite to the surface on which the adhesive layer is laminated.
[0186] The antistatic agent may be an ionic compound. The ionic compound is a compound having an inorganic cation or an organic cation and an inorganic anion or an organic anion. Two or more kinds of ionic compounds may be used.
[0187] The adhesion strength of the surface protection film to the optical laminate 1 at a temperature of 23°C and a relative humidity of 55% is preferably 0.01 N / 25 mm or more, more preferably 0.03 N / 25 mm or more, and even more preferably 0.08 N / 25 mm or more, and is preferably 0.5 N / 25 mm or less, more preferably 0.4 N / 25 mm or less, and even more preferably 0.3 N / 25 mm or less.
[0188] The adhesion can be measured by the following procedure. The laminate with the surface protective film is cut into a rectangle of any size and attached to a glass substrate or the like to prepare a test piece. A 180° peel test is performed on this evaluation sample at a travel speed of 300 mm / min in accordance with JIS K6854-2:1999 "Adhesives - Peel adhesion strength test method - Part 2: 180° peel", and the peel strength measured is taken as the adhesion.
[0189] When the surface protection film is a resin film for surface protection film having an adhesive layer provided thereon, the thickness of the adhesive layer is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 15 μm or more, and is preferably 30 μm or less, more preferably 25 μm or less, and even more preferably 20 μm or less.
[0190] Examples of the resin constituting the resin film for surface protection film include polyolefin resins such as polyethylene resins and polypropylene resins; cyclic polyolefin resins; polyester resins such as polyethylene terephthalate and polyethylene naphthalate; polycarbonate resins; (meth)acrylic resins, etc. Among these, polyester resins such as polyethylene terephthalate are preferred. The resin film for surface protection film may have a single layer structure, or a multilayer structure of two or more layers. The resin film for surface protection film may be a film that has been subjected to a stretching process such as uniaxial stretching or biaxial stretching.
[0191] The above-mentioned surface protection film can be obtained by applying an adhesive to the surface of the resin film for surface protection film, followed by drying, etc. to form an adhesive layer. The self-adhesive film that can be used as the surface protection film is a film that can adhere by itself and maintain the adhered state without providing a means for adhesion such as an adhesive layer, etc. The self-adhesive film can be formed using, for example, a polypropylene-based resin, a polyethylene-based resin, or the like.
[0192] (6) Image display device The image display device includes an optical laminate and an image display element (such as an organic EL display element). The optical laminate is disposed on the viewing side of the image display element. The optical laminate can be attached to the image display element using a pressure-sensitive adhesive layer.
[0193] The image display device is not particularly limited, and examples thereof include image display devices such as organic electroluminescence (organic EL) display devices, inorganic electroluminescence (inorganic EL) display devices, liquid crystal display devices, and electroluminescence display devices.
[0194] The image display device can be used as mobile devices such as smartphones and tablets, televisions, digital photo frames, electronic signs, measuring instruments or gauges, office equipment, medical equipment, computing equipment, and the like. EXAMPLES
[0195] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples. In the examples, "%" and "parts" mean mass% and mass parts, respectively, unless otherwise specified.
[0196] <Measurement and evaluation methods> (1) Measurement of boron content in polarizers 0.2 g of the polarizer was dissolved in 200 g of a 1.9% by mass mannitol aqueous solution. The resulting aqueous solution was titrated with a 1 mol / L NaOH aqueous solution, and the boron content (mass%) of the polarizer was calculated by comparing the amount of NaOH solution required for neutralization with the calibration curve. The results are shown in Table 5.
[0197] (2) Calculation of boric acid cross-linking index The cross section of the polarizing plate was processed using an ultramicrotome (manufactured by LEICA under the product name "LEICA Ultramicrotome EM UC7i"). The cross section of the polarizing plate obtained was measured at the center position in the thickness direction of the polarizer using a laser Raman spectrophotometer (product name: "NRS-5100" manufactured by JASCO Corporation) under the following conditions at a wave number of 780 cm -1 Raman scattering intensity at 850 cm -1 The Raman scattering light intensity at each wavenumber was then calculated, and the Raman scattering light intensities at these wavenumbers were then divided (wavenumber 780 cm -1 Raman scattering intensity at 850 cm -1 The boric acid crosslinking index was calculated from the Raman scattering intensity at 100 nm.
[0198] Excitation wavelength: 532nm Grating: 600 l / mm Slit width: 100×1000μm Aperture: φ40μm Objective lens: 100x Objective lens: 100x (3) Measurement of moisture permeability of peelable film The moisture permeability was measured based on JIS Z 0208. The temperature and humidity conditions were a temperature of 40° C. and a relative humidity of 90% RH.
[0199] (4) Measurement of luminosity-corrected single transmittance and luminosity-corrected polarization The single transmittance and luminosity-corrected polarization degree of the optical laminate were measured by a spectrophotometer with an integrating sphere (V7100, manufactured by JASCO Corporation) by making linearly polarized light from a prism incident on the polarizer side of the optical laminate. The MD transmittance and TD transmittance were obtained in the wavelength range of 380 nm to 780 nm, and the single transmittance and polarization degree at each wavelength were calculated based on formulas (A) and (B). Furthermore, luminosity correction was performed using a 2-degree visual field (C light source) according to JISZ8701, and the luminosity-corrected single transmittance (Ty) and luminosity-corrected polarization degree (Py) were obtained. The "MD transmittance" is the transmittance when the direction of the polarized light coming out of the Glan-Thompson prism is parallel to the transmission axis of the polarizing plate sample. In formulas (A) and (B), the "MD transmittance" is represented as "MD". In addition, the "TD transmittance" is the transmittance when the direction of the polarized light exiting the Glan-Thompson prism is perpendicular to the transmission axis of the polarizing plate sample, and in formulas (A) and (B), the "TD transmittance" is represented as "TD."
[0200] Single layer transmittance (%) = (MD + TD) / 2 Formula (A) Degree of polarization (%)={(MD-TD) / (MD+TD)}×100 Formula (B) (5) Weather resistance test of optical laminate The optical laminate obtained in the examples was cut into a square having a size of 30 mm x 30 mm. At this time, the cut was made so that the absorption axis of the polarizer and the sides of the square were parallel to each other. The cut optical laminate was attached to a 40 mm x 40 mm alkali-free glass (manufactured by Corning, product number: EAGLE XG (registered trademark)) via a pressure-sensitive adhesive layer (2) to prepare an evaluation sample. The luminous efficiency-corrected polarization degree Py was measured for each evaluation sample.
[0201] Next, the evaluation sample was placed on an aluminum plate (reflector) so that ultraviolet rays were irradiated from the polarizer side, and was placed in a Sunshine Weather Meter (manufactured by Suga Test Instruments Co., Ltd.) for 240 hours under conditions of a black panel temperature of 63°C and a relative humidity of 50%, to perform a weather resistance test. After the test, the luminosity-corrected polarization degree Py of the evaluation sample was measured. The absolute value ΔPy of the difference in luminosity-corrected polarization degree Py before and after the test was calculated.
[0202] (6) Edge protrusion test for optical laminate The optical laminate obtained in the examples was cut into a rectangle of 100 mm x 50 mm so that the absorption axis of the polarizer was parallel to the long side. The cut optical laminate was attached to an alkali-free glass (manufactured by Corning, product number: EAGLE XG (registered trademark)) having a thickness of 0.7 mm via an adhesive to prepare a sample for evaluation. A heat resistance test was performed in which the evaluation sample was stored in a dryer at a temperature of 105°C for 30 minutes, and the sample after the test was stored in an environment of 23°C and 55% humidity for 30 minutes, after which the "height difference of the end deformation" was measured.
[0203] "Elevation difference of end deformation" FIG. 4 shows the evaluation sample. For the measurement, a three-dimensional microscope "PLμ2300" manufactured by Sensofar was used, and the height of deformation was measured in a width of 800 μm from the end face (A) of the center of the short side of the polarizing plate to the in-plane (A') toward the center of the in-plane direction using the confocal mode (see Figure 4). The magnification of the objective lens during the measurement was 20 times. Figure 5 shows an example of the result of measuring the height of deformation from the end face (A) of the polarizing plate toward the in-plane (A'). A negative value for the height of deformation means that the optical laminate bonded to the non-alkali glass is deformed toward the non-alkali glass side. A positive value for the height of deformation means that the optical laminate bonded to the non-alkali glass is deformed toward the opposite side to the non-alkali glass side. From the obtained results, the difference between the maximum and minimum values of the height of deformation was calculated as the "height difference of the edge deformation".
[0204] The evaluation criteria for the edge swelling are as follows: ◎◎(Excellent): The height difference of the end deformation is less than 3 μm. ◎(Good): The height difference of the end deformation is 3 μm or more and less than 5 μm.
[0205] ○(Acceptable): The height difference of the end deformation is 5 μm or more and less than 7 μm. × (Fail): The height difference of the end deformation is 7 μm or more. (7) Measurement of absorbance of laminate A laminate was prepared by laminating the first bonding layer 30a, the first liquid crystal cured layer 201, the third bonding layer 30c, the second liquid crystal cured layer 202, and the second bonding layer 30b. The laminate was attached to glass via the second bonding layer 30b. A cycloolefin polymer (COP) film (ZF-14 manufactured by Zeon Corporation) was attached to the first liquid crystal cured layer 201 via the first bonding layer 30a. In this manner, a laminate for evaluation was prepared.
[0206] The laminate for evaluation was set in a spectrophotometer UV-2450 (manufactured by Shimadzu Corporation), and the absorbance was measured in the wavelength range of 300 to 800 nm in 1 nm steps by the double beam method. The absorbance at a wavelength of 340 nm of the prepared laminate is shown in Table 5. The absorbance at a wavelength of 340 nm of both the glass alone and the COP film alone was 0.
[0207] <Preparation of Components of Optical Stack> (1) Preparation of polarizer (1) A polyvinyl alcohol film having a thickness of 20 μm, a degree of polymerization of 2400, and a degree of saponification of 99% or more was uniaxially stretched to a stretching ratio of 4.6 times on a heated roll and, while maintaining the tension, was immersed for 60 seconds at 28° C. in a dye bath containing 0.05 parts by mass of iodine and 5 parts by mass of potassium iodide per 100 parts by mass of water.
[0208] Next, the film was immersed in a boric acid aqueous solution 1 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water at 65° C. for 110 seconds. Next, the film was immersed in a boric acid aqueous solution 2 containing 2.3 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water at 68° C. for 30 seconds. After that, the film was washed with pure water at 10° C. and dried to obtain a polarizer (1). The polarizer (1) had a thickness of 8 μm and a boron content of 3.2% by mass. The boric acid crosslinking index was 0.8.
[0209] (2) Preparation of polarizer (2) A polyvinyl alcohol film having a thickness of 20 μm, a degree of polymerization of 2400, and a degree of saponification of 99% or more was uniaxially stretched to a stretching ratio of 4.6 times on a heated roll and, while maintaining the tension, was immersed for 60 seconds at 28° C. in a dye bath containing 0.05 parts by mass of iodine and 5 parts by mass of potassium iodide per 100 parts by mass of water.
[0210] Next, the film was immersed in a boric acid aqueous solution 1 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water at 65°C for 110 seconds. Next, the film was immersed in a boric acid aqueous solution 2 containing 5.5 parts by mass of boric acid and 15 parts by mass of potassium iodide per 100 parts by mass of water at 68°C for 30 seconds. After that, the film was washed with pure water at 10°C and dried to obtain a polarizer (2). The polarizer (2) had a thickness of 8 μm and a boron content of 4.3% by mass. The boric acid crosslinking index was 1.2.
[0211] (3) Preparation of polarizer (3) A polarizer (3) was obtained in the same manner as the polarizer (2), except that the stretching ratio was changed to 4.1 times, the temperature of the boric acid aqueous solution 1 was changed to 64° C., and the temperature of the boric acid aqueous solution 2 was changed to 67° C. The polarizer (3) had a thickness of 8 μm and a boron content of 4.3% by mass. The boric acid crosslinking index was 1.1.
[0212] (4) Preparation of peelable film, protective film, and surface protective film The following release films, protective films, and surface protective films were prepared. Release film A: TD80UL, a triacetyl cellulose film manufactured by Fujifilm Corporation. It had a thickness of 80 μm and a moisture permeability of 502 g / m2·24 hr. Protective film B: a COP of 23 μm. It does not absorb ultraviolet light. Surface protective film C: An acrylic adhesive layer of 15 μm was formed on a polyester resin film of 38 μm in thickness to produce a surface protective film C having an adhesive layer of 53 μm in thickness.
[0213] (5) Preparation of linear polarizing plate (1) A peelable film A was laminated to both sides of the prepared polarizer (1) via pure water using a roll laminator, and then dried at 80°C for 3 minutes to obtain a linear polarizing plate (1) having the peelable film A on both sides of the polarizer (1).
[0214] The release films A on both sides of the linear polarizing plate (1) were peeled off and removed, and the luminous efficiency-corrected single transmittance measured for the polarizer (1) alone was 42.3%, and the luminous efficiency-corrected polarization degree was 99.99%. (6) Preparation of linear polarizing plate (2) A linear polarizing plate (2) was produced in the same manner as the linear polarizing plate (1), except that the polarizing element (1) was changed to the polarizing element (2).
[0215] The release films A on both sides of the linear polarizing plate (2) were peeled off and removed, and the luminous efficacy-corrected single transmittance measured for the polarizer (2) alone was 42.4%, and the luminous efficacy-corrected polarization degree was 99.98%. (7) Preparation of linear polarizing plate (3) A protective film B was attached to one surface of the prepared polarizer (3) via a water-based adhesive, and a peelable film A was attached to the opposite surface of the protective film B via pure water using a roll laminator, and then the resulting film was dried at 80° C. for 3 minutes to obtain a linear polarizing plate (3). The linear polarizing plate (3) is formed by laminating the peelable film A, the polarizer (3), an adhesive layer, and the protective film B in this order.
[0216] (8) Liquid crystal hardening layer A The following retardation film (Z1) was prepared as the second liquid crystal cured layer A. The following retardation film (Z2) was prepared as the first liquid crystal cured layer A.
[0217] [Preparation of Oriented Polymer Composition (1)] Water was added to commercially available polyvinyl alcohol (polyvinyl alcohol 1000 fully saponified type, manufactured by Wako Pure Chemical Industries, Ltd.), and the mixture was heated at 100° C. for 1 hour to obtain an oriented polymer composition (1).
[0218] [Production of polymerizable liquid crystal compounds] Polymerizable liquid crystal compound (A1) and polymerizable liquid crystal compound (A2) having the structures shown below were prepared. Polymerizable liquid crystal compound (A1) and polymerizable liquid crystal compound (A2) were prepared in the same manner as described in JP-A-2010-244038.
[0219] Polymerizable liquid crystal compound (A1): A compound represented by the following formula:
[0220] [ka]
[0221] Polymerizable liquid crystal compound (A2): A compound represented by the following formula:
[0222] [ka]
[0223] [Preparation of Retardation Layer Forming Composition (Y1)] Polymerizable liquid crystal compound Paliocolor LC242 (manufactured by BASF Japan), leveling agent "BYK-361N" (manufactured by BYK-Chemie), and photopolymerization initiator "Omnirad907" (manufactured by IGM Resin BV) were added. Furthermore, propylene glycol 1-monomethyl ether 2-acetate (PGME) was added, and the mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation layer forming composition (Y1).
[0224] [Table 1]
[0225] Polymerizable liquid crystal compound LC242: a compound represented by the following formula
[0226] [ka]
[0227] [Preparation of Retardation Layer Forming Composition (Y2)] The polymerizable liquid crystal compound (A1) and the polymerizable liquid crystal compound (A2) were mixed in a mass ratio of 80:20 to obtain a mixture. To 100 parts of the obtained mixture, parts of a leveling agent "Megafac F-556" (manufactured by DIC Corporation), parts of a photopolymerization initiator "Omnirad907" (manufactured by IGM Resin BV), and an ionic compound (B) were added. Furthermore, cyclopentanone was added, and the mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation layer forming composition (Y2).
[0228] [Table 2]
[0229] Ionic compound (B): a compound represented by the following formula:
[0230] [ka]
[0231] [Preparation of retardation film (Z1)] The oriented polymer composition (1) was applied to a rectangular cut triacetyl cellulose film (TAC) (KC4UY, manufactured by Konica Minolta, Inc.), and after heating and drying, an oriented polymer film having a thickness of 100 nm was formed. The surface of the obtained oriented polymer film was subjected to a rubbing treatment at an angle of 15° from the longitudinal direction of the TAC, and the retardation layer forming composition (Y1) was applied thereon by a bar coater. The obtained coating film was dried at 100°C for 1 minute, and then cooled to room temperature to obtain a dried film. Next, a high-pressure mercury lamp (Uniquer VB-15201BY-A, manufactured by Ushio Inc.) was used to expose the film to light in a nitrogen atmosphere at an exposure dose of 1000 mJ / cm2. 2 By irradiating the dried film with ultraviolet light (365 nm standard), a retardation layer (X1) was formed in which the polymerizable liquid crystal compound was cured in a state of being aligned horizontally relative to the substrate surface, and a retardation film (Z1) consisting of TAC / alignment film / retardation layer (X1) (horizontally aligned liquid crystal cured film) was obtained. The thickness of the obtained retardation layer (X1) was measured with a laser microscope and found to be 1.0 μm. The in-plane retardation value was measured using KOBRA-WR manufactured by Oji Scientific Instruments Co., Ltd. As a result, the in-plane retardation value at a wavelength of 550 nm was Re(550)=140 nm. Note that the retardation value of TAC at a wavelength of 550 nm is approximately 0, so there is no effect on the optical properties. The orientation angle was 15° with respect to the longitudinal direction of the TAC.
[0232] [Preparation of retardation film (Z2)] A rectangular cut-out cycloolefin polymer (COP) (ZF14, manufactured by Zeon Corporation) was subjected to corona treatment using a corona treatment device (AGF-B10; manufactured by Kasuga Electric Co., Ltd.), and then an oriented polymer composition (1) was applied thereto. After drying by heating, an oriented polymer film having a thickness of 100 nm was formed. The surface of the obtained oriented polymer film was subjected to rubbing treatment at an angle of 75° from the longitudinal direction of the COP, and a retardation layer forming composition (Y2) was applied thereon using a bar coater. The obtained coating film was dried at 120°C for 2 minutes, and then exposed to 1000 mJ / cm2 at 80°C under a nitrogen atmosphere using a high-pressure mercury lamp (Uniquer VB-15201BY-A, manufactured by Ushio Electric Co., Ltd.). 2The dried film was irradiated with ultraviolet light (365 nm standard) to form a retardation layer (X2) in which the optical axis of the polymerizable liquid crystal compound was aligned horizontally relative to the substrate surface, and a retardation film (Z2) consisting of COP / alignment film / retardation layer (X2) was obtained. The thickness of the obtained retardation layer (X2) was measured with a laser microscope and found to be 1.8 μm. The in-plane retardation value was measured using KOBRA-WR manufactured by Oji Scientific Instruments Co., Ltd. As a result, the in-plane retardation value at a wavelength of 550 nm was Re(550)=270 nm. Note that the retardation value of the COP at a wavelength of 550 nm is approximately 0, so there is no effect on the optical properties. The orientation angle was 75° with respect to the longitudinal direction of the COP.
[0233] (9) Preparation of active energy ray curable adhesive A The components listed below were mixed and then degassed to prepare an active energy ray-curable adhesive A.
[0234] [Cationic polymerizable compounds] Neopentyl glycol diglycidyl ether (product name: EX-211L, manufactured by Nagase ChemteX Corporation) 30 parts by mass 13 parts by mass of 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane (product name: OXT-221, manufactured by Toagosei Co., Ltd.) Bisphenol A epoxy resin (product name: EP-4100E, ADEKA Corporation, viscosity 13 Pa·s (temperature 25°C)) 45 parts by weight ·Aromatic-containing oxetane compound (product name: TCM-104, manufactured by TRONLY) 12 parts by mass [Photocationic polymerization initiator] CPI-100P, San-Apro Co., Ltd., 50% propylene carbonate solution, 2.25 parts by weight (solid content) [Photosensitizer] 1,4-diethoxynaphthalene 1 part by mass (10) Preparation of retardation plate A with substrate layer The surface of the first liquid crystal cured layer A (1 / 2 wavelength retardation layer) on the base layer and the surface of the second liquid crystal cured layer A (1 / 4 wavelength retardation layer) on the base layer were each subjected to a corona treatment. The corona-treated surfaces of these two retardation layers were bonded together using the active energy ray curable adhesive A prepared above so that the angle between the slow axes of these two retardation layers was 60°. Thereafter, an ultraviolet ray irradiation device (manufactured by Fusion UV Systems Co., Ltd.) was used from the 1 / 4 wavelength retardation layer side to irradiate the layers with an integrated light amount of 400 mJ / cm. 2 The active energy ray curable adhesive A was cured by irradiating with ultraviolet light (UV-B) to form an adhesive layer. The lamination was performed using a laminator, and the active energy ray curable adhesive A was applied so that the adhesive layer after curing had a thickness of 2 μm. As a result, a retardation plate A with a base layer was obtained in which the base layer, the alignment layer, the 1 / 2 wavelength retardation layer (first liquid crystal cured layer), the adhesive layer (third lamination layer), the 1 / 4 wavelength retardation layer (second liquid crystal cured layer), the alignment layer, and the base layer were laminated in this order. The total thickness of the 1 / 2 wavelength retardation layer (first liquid crystal cured layer), the adhesive layer (third lamination layer), and the 1 / 4 wavelength retardation layer (second liquid crystal cured layer) was 4.8 μm.
[0235] (11) Preparation of first liquid crystal cured layer B As the first liquid crystal cured layer B, the following retardation film (Z) was prepared. [Preparation of composition (X) for forming photo-alignment film] The photoalignment material (weight average molecular weight: 50,000, m:n = 50:50) having the following structure was produced according to the method described in JP 2021-196514 A. Two parts of the photoalignment material and 98 parts of cyclopentanone (solvent) were mixed as components, and the resulting mixture was stirred at 80 ° C. for 1 hour to prepare a composition (X) for forming a photoalignment film.
[0236] Photoalignment material: a compound represented by the following formula
[0237] [ka]
[0238] [Production of polymerizable liquid crystal compounds] The polymerizable liquid crystal compound (A3) and the polymerizable liquid crystal compound (A4) having the structures shown below were prepared. The polymerizable liquid crystal compound (A3) was prepared in the same manner as described in JP-A-2019-003177. The polymerizable liquid crystal compound (A4) was prepared in the same manner as described in JP-A-2009-173893.
[0239] Polymerizable liquid crystal compound (A3): A compound represented by the following formula:
[0240] [ka]
[0241] Polymerizable liquid crystal compound (A4): A compound represented by the following formula:
[0242] [ka]
[0243] A solution was obtained by dissolving 1 mg of the polymerizable liquid crystal compound (A3) in 10 mL of chloroform. The obtained solution was placed in a measurement cell with an optical path length of 1 cm, and the measurement sample was set in an ultraviolet-visible spectrophotometer (Shimadzu Corporation, "UV-2450") to measure the absorption spectrum. The wavelength at which the maximum absorbance was obtained was read from the obtained absorption spectrum, and the maximum absorption wavelength λmax in the wavelength range of 300 to 400 nm was 356 nm.
[0244] [Preparation of Retardation Layer Forming Composition (Y)] The polymerizable liquid crystal compound (A3) and the polymerizable liquid crystal compound (A4) were mixed in a mass ratio of 90:10 to obtain a mixture. 0.1 parts of a leveling agent "BYK-361N" (manufactured by BM Chemie) and 3 parts of a photopolymerization initiator "Irgacure OXE-03" (manufactured by BASF Japan Ltd.) were added to 100 parts of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration was 13%. The mixture was stirred at a temperature of 80°C for 1 hour to prepare a retardation layer forming composition (Y).
[0245] [Table 3]
[0246] [Preparation of retardation film (Z)] The photo-alignment film-forming composition (X) was applied to a biaxially oriented polyethylene terephthalate (PET) film (Diafoil, manufactured by Mitsubishi Plastics, Inc.) as the substrate C using a bar coater. The resulting coating film was dried at 120°C for 2 minutes, and then cooled to room temperature to form a dry film. Thereafter, a UV irradiation device (SPOT CURE SP-9, manufactured by Ushio Inc.) was used to irradiate the film with 100 mJ of polarized ultraviolet light (based on 313 nm) to obtain a photo-alignment film D. The thickness of the photo-alignment film D measured using an ellipsometer M-220 manufactured by JASCO Corporation was 100 nm.
[0247] The above-mentioned retardation layer forming composition (Y) was applied onto the obtained photo-alignment film D using a bar coater to form a coating film. This coating film was dried by heating at 120°C for 2 minutes, and then cooled to room temperature to obtain a dried film. Next, using a high-pressure mercury lamp ("Uniquer VB-15201BY-A" manufactured by Ushio Inc.), the exposure amount was 500 mJ / cm2 in a nitrogen atmosphere. 2 By irradiating the dried film with ultraviolet light (365 nm standard), a retardation layer was formed in which the polymerizable liquid crystal compound was cured in a state of being aligned horizontally relative to the substrate surface, and a retardation film (Z) consisting of substrate C / photo-aligned film D / retardation layer (horizontally aligned liquid crystal cured film) was obtained. The thickness of the retardation layer measured using a laser microscope LEXT OLS4100 manufactured by Olympus Corporation was 2.0 μm.
[0248] The liquid crystal side of the retardation film (Z) was corona-treated, and the film was attached to glass via a 25 μm pressure-sensitive adhesive made by Lintec Corporation, and the PET film was peeled off and removed. The in-plane retardation values were measured using a KOBRA-WR made by Oji Scientific Instruments Co., Ltd. The in-plane retardation values for light with wavelengths of 450 nm, 550 nm, and 650 nm were calculated from Cauchy's dispersion formula obtained from the measurement results of the in-plane retardation values for light with wavelengths of 448.2 nm, 498.6 nm, 548.4 nm, 587.3 nm, 628.7 nm, and 748.6 nm.
[0249] As a result, the in-plane retardation values were Re(450)=122 nm, Re(550)=140 nm, and Re(650)=144 nm, and the relationship between the in-plane retardation values at each wavelength was as follows:
[0250] Re(450) / Re(550)=0.87 Re(650) / Re(550)=1.03 (In the formula, Re(450) represents an in-plane retardation value for light with a wavelength of 450 nm, Re(550) represents an in-plane retardation value for light with a wavelength of 550 nm, and Re(650) represents an in-plane retardation value for light with a wavelength of 650 nm.) (12) Preparation of second liquid crystal cured layer B As the second liquid crystal cured layer B, the following retardation film (1) was prepared.
[0251] The retardation layer forming composition (1) was prepared by mixing a photopolymerizable nematic liquid crystal compound (RMM28B, manufactured by Merck) and a solvent so that the solid content was 1 to 1.5 g. The solvent used was a mixed solvent obtained by mixing methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and cyclohexanone (CHN) in a mass ratio (MEK:MIBK:CHN) of 35:30:35.
[0252] A polyethylene terephthalate (PET) film having a thickness of 38 μm was prepared as a substrate layer. A composition for forming a vertical alignment film was applied to one side of the substrate layer to a thickness of 3 μm, and a coating density of 200 mJ / cm 2 A vertical alignment film was formed by irradiating the liquid crystal layer with ultraviolet light of 1000 nm.
[0253] The composition for forming the retardation layer (1) was applied onto the vertical alignment film by die coating. The amount of coating was 4 to 5 g (wet). The coating was dried at a drying temperature of 75° C. for a drying time of 120 seconds. Thereafter, the coating was irradiated with ultraviolet (UV) rays to polymerize the polymerizable liquid crystal compound.
[0254] In this way, a retardation film (1) was obtained in which a layer of the cured polymerizable liquid crystal compound (second liquid crystal cured layer B), a vertical alignment film, and a base layer were laminated in this order. The second liquid crystal cured layer B was a positive C plate. The total thickness of the second liquid crystal cured layer B and the alignment film was 4 μm.
[0255] (13) Preparation of active energy ray curable adhesive B The components shown below were mixed to prepare an active energy ray-curable adhesive B. 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (product name: CEL2021P, manufactured by Daicel Corporation): 70 parts by mass Neopentyl glycol diglycidyl ether (product name: EX-211, manufactured by Nagase ChemteX Corporation): 20 parts by mass 2-Ethylhexyl glycidyl ether (product name: EX-121, manufactured by Nagase ChemteX Corporation): 10 parts by mass Cationic polymerization initiator (product name: CPI-100_50% solution, manufactured by San-Apro Co., Ltd.): 4.5 parts by weight (actual solid content 2.25 parts by weight) 1,4-diethoxynaphthalene: 2 parts by weight (14) Preparation of retardation plate B with substrate layer The first liquid crystal cured layer B and the second liquid crystal cured layer B were bonded together with an active energy ray curable adhesive B (thickness 1 μm) so that the liquid crystal cured layer surface (the surface opposite to the substrate film) of each layer was the bonding surface. The active energy ray curable adhesive B was cured by irradiating ultraviolet rays to obtain a retardation plate B with a substrate layer, in which the substrate layer, the alignment layer, the first liquid crystal cured layer B, the adhesive layer (third bonding layer), the second liquid crystal cured layer B, the alignment layer, and the substrate layer were laminated in this order. The thickness of the retardation laminate including the first liquid crystal cured layer B, the adhesive layer (third bonding layer), and the second liquid crystal cured layer B was 7 μm. The retardation plate B with the substrate layer has ultraviolet ray absorbing properties.
[0256] (15) Preparation of adhesive layer The following adhesive layers were prepared. [Adhesive layer (1A)] (1-1) Preparation of acrylic resin solution (1A) A mixed solution of 100 parts of ethyl acetate, 99.0 parts of butyl acrylate, 0.5 parts of 2-hydroxyethyl acrylate, and 0.5 parts of acrylic acid was charged into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer, and a stirrer, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while raising the internal temperature to 55 ° C. Then, a solution of 0.12 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts of ethyl acetate was added in its entirety. After adding the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54 to 56 ° C., and the addition of ethyl acetate was stopped when the concentration of the (meth)acrylic resin became 35% by mass, and the temperature was kept at this temperature until 6 hours had passed since the start of the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the (meth)acrylic resin to 20% by mass, and an acrylic resin solution (1A) was prepared. The weight average molecular weight Mw of the obtained acrylic resin was 1.7 million, and the molecular weight distribution Mw / Mn was 3.9. Note that Mw and Mn were measured using a GPC apparatus with a TSKgel GMH column manufactured by Tosoh Corporation. HR Two "-H(S)" were connected in series, and tetrahydrofuran was used as the eluent. The sample concentration was 2 mg / mL, the sample amount was 100 μL, the temperature was 40°C, and the flow rate was 1 mL / min. The measurements were performed in terms of standard polystyrene.
[0257] (1-2) Preparation of the Adhesive Composition (1A) To 80 parts by solid content of the acrylic resin solution (1A) obtained in (1-1), 20 parts by solid content of a bifunctional acrylate (obtained from Shin-Nakamura Chemical Co., Ltd.; product number "A-DOG"), 2.5 parts of a crosslinking agent (manufactured by Mitsui Chemicals: trade name "D-101E" (ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate (solid content concentration: 75% by mass))) based on the active ingredient, 1.5 parts of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name "Irgacure 500"), and 0.3 part of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd.: trade name "KBM-403") were added. Further, ethyl acetate was added so that the solid content concentration became 13% to obtain the adhesive composition (1A).
[0258] A-DOG is a diacrylate of an acetal compound of hydroxypivalaldehyde and trimethylolpropane and has the structure of the following formula.
[0259] [Chemical Formula]
[0260] (1-3) Preparation of the Adhesive Sheet (1A) The adhesive composition (1A) prepared in (1-2) was applied to the release-treated surface of a separator film made of a polyethylene terephthalate film with release treatment [manufactured by Mitsubishi Chemical Corporation: MRV (V04) (thickness: 38 μm)] using an applicator so that the thickness after drying became 5 μm, and dried at 100°C for 1 minute to form an adhesive layer. Next, the surface of the obtained adhesive layer on the side opposite to the separator film was bonded to the release-treated surface of a separator film made of a polyethylene terephthalate film with release treatment [manufactured by Mitsubishi Chemical Corporation: MRF (thickness: 38 μm)]. Subsequently, ultraviolet rays were irradiated under the following conditions to prepare the adhesive sheet (1A) as the adhesive layer (1A).
[0261] [UV Irradiation Conditions] Fusion UV lamp system (manufactured by Fusion UV Systems) H bulb used Accumulated light output 250mJ / cm 2 [Adhesive layer (1B)] (2-1) Preparation of acrylic resin (A-1) A mixed solution of 86.4 parts of ethyl acetate, 61.9 parts of butyl acrylate, and 1.9 parts of 2-hydroxyethyl acrylate was charged as a solvent in a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirrer, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while the internal temperature was raised to 60°C. Then, a solution of 0.4 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts of ethyl acetate was added in its entirety. The resulting mixture was kept at 60°C for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 50-70°C, and when the concentration of the acrylic resin reached 35%, the addition of ethyl acetate was stopped, and the temperature was kept at this temperature until 12 hours had passed since the start of the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the acrylic resin to 20%, and an ethyl acetate solution of the acrylic resin was prepared. The resulting acrylic resin had a weight average molecular weight Mw of 600,000 in terms of polystyrene by GPC, and Mw / Mn of 7.0. This is referred to as acrylic resin (A-1). The glass transition temperature measured by DSC was −52.9° C.
[0262] In an ethyl acetate solution of acrylic resin (A-1) (resin concentration: 20%), 0.5 parts of a crosslinker (Coronate L, solid content 75%: manufactured by Tosoh), 0.5 parts of a silane compound (manufactured by Shin-Etsu Chemical Co., Ltd.: KBM-403) and 3.7 parts of a compound (light selective absorber) represented by the following formula (aa2) described as a light selective absorbing compound (2) in Synthesis Example 2 described in paragraph
[0142] of JP-A-2019-007001 were mixed with each other, and 2-butanone was added so that the solid content concentration was 14%, to obtain a pressure-sensitive adhesive composition (1). The amount of the crosslinker (Coronate L) is the number of parts by mass as an active ingredient.
[0263] [ka]
[0264] The adhesive composition (1) prepared above was applied to the release-treated surface of a release-treated polyethylene terephthalate film (SP-PLR382050 manufactured by Lintec Corporation, hereinafter abbreviated as "separator") using an applicator so that the adhesive layer would have a thickness of 5 μm after drying, and then dried at 100° C. for 1 minute to prepare an adhesive layer. The resulting adhesive layer was designated adhesive layer (1B) (hereinafter also referred to as light-selective absorbing adhesive 1). As shown in Table 4, the content of the light-selective absorbing agent per unit area of light-selective absorbing adhesive 1 was 0.2 (g / m 2 ) was.
[0265] [Table 4]
[0266] The light selective absorbing pressure sensitive adhesive layer of this example is formed from a pressure sensitive adhesive composition containing at least a (meth)acrylic resin and a light selective absorbing compound. The pressure-sensitive adhesive composition preferably further contains a crosslinking agent.
[0267] The light selective absorption compound is not particularly limited as long as it is a compound that selectively absorbs light with a wavelength of 340 nm. Examples of compounds that selectively absorb light with a wavelength of 340 nm include ultraviolet absorbers. The ultraviolet absorbers are not particularly limited, but include organic ultraviolet absorbers such as oxybenzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, salicylic acid ester-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, and triazine-based ultraviolet absorbers. More specifically, examples include 5-chloro-2-(3,5-di-sec-butyl-2-hydroxylphenyl)-2H-benzotriazole, (2-2H-benzotriazol-2-yl)-6-(straight-chain and side-chain dodecyl)-4-methylphenol, 2-hydroxy-4-benzyloxybenzophenone, and 2,4-benzyloxybenzophenone. These organic ultraviolet absorbers may be used alone or in combination of two or more.
[0268] The ultraviolet absorber may be a commercially available product. Examples of triazine-based ultraviolet absorbers include "Kemisorb 102" manufactured by Chemipro Chemical Co., Ltd., "ADEKA STAB LA46" and "ADEKA STAB LAF70" manufactured by ADEKA Corporation, and "TINUVIN 109", "TINUVIN 171", "TINUVIN 234", "TINUVIN 326", "TINUVIN 327", "TINUVIN 328", "TINUVIN 928", "TINUVIN 400", "TINUVIN 460", "TINUVIN 405", and "TINUVIN 477" manufactured by BASF Japan Ltd. Examples of benzotriazole-based ultraviolet absorbers include "ADEKA STAB LA31" and "ADEKA STAB LA36" manufactured by ADEKA CORPORATION; "SUMISORB 200," "SUMISORB 250," "SUMISORB 300," "SUMISORB 340," and "SUMISORB 350" manufactured by Sumika Chemtex Corporation; "Kemisorb 74," "Kemisorb 79," and "Kemisorb 279" manufactured by Chemipro Chemicals Co., Ltd.; and "TINUVIN 99-2," "TINUVIN 900," and "TINUVIN 928" manufactured by BASF.
[0269] The ultraviolet absorbing agent may be an inorganic ultraviolet absorbing agent. Examples of the inorganic ultraviolet absorbing agent include titanium oxide, zinc oxide, indium oxide, tin oxide, talc, kaolin, calcium carbonate, titanium oxide-based composite oxide, zinc oxide-based composite oxide, ITO (tin-doped indium oxide), and ATO (antimony-doped tin oxide). Examples of the titanium oxide-based composite oxide include zinc oxide doped with silica and alumina. These inorganic ultraviolet absorbing agents may be used alone or in combination of two or more. In addition, an organic ultraviolet absorbing agent and an inorganic ultraviolet absorbing agent may be used in combination.
[0270] The weight average molecular weight (Mw) of the (meth)acrylic resin for forming the pressure-sensitive adhesive layer is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC) under the following conditions.
[0271] [Measurement conditions] GPC measuring device: Tosoh Corporation, HLC-8020 GPC columns (passed in the following order): Tosoh Corporation TSK guard column HXL-H TSK gel GMHXL (×2) TSK gel G2000HXL Measurement solvent: Tetrahydrofuran Measurement temperature: 40℃ [Adhesive layer (1C)] An adhesive layer (1C) (hereinafter also referred to as light-selective absorbing adhesive 2) was produced in the same manner as for the adhesive layer (1B), except that the blending amount of the light-selective absorbing agent was 4.8 parts and the thickness of the adhesive layer after drying was 17 μm. As shown in Table 4, the content of the light-selective absorbing agent per unit area of the light-selective absorbing adhesive 2 was 0.9 (g / m 2 ) was.
[0272] [Adhesive layer (1D)] The adhesive layer (1B) (hereinafter also referred to as light-selective absorbing adhesive 3) was produced in the same manner as for the adhesive layer (1B), except that the blending amount of the light-selective absorbing agent was 6.3 parts and the thickness of the adhesive layer after drying was 17 μm. As shown in Table 4, the content of the light-selective absorbing agent per unit area of the light-selective absorbing adhesive 3 was 1.2 (g / m 2 ) was.
[0273] [Adhesive layer (2)] (3-1) Preparation of acrylic resin solution (2) A mixed solution of 81.8 parts of ethyl acetate, 90.0 parts of butyl acrylate, 5.0 parts of methyl acrylate and 5.0 parts of acrylic acid was charged into a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer and a stirrer, and the air in the apparatus was replaced with nitrogen gas to make it oxygen-free, while raising the internal temperature to 55 ° C. Then, a solution of 0.15 parts of azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts of ethyl acetate was added in its entirety. After adding the polymerization initiator, the temperature was maintained for 1 hour, and then ethyl acetate was continuously added to the reaction vessel at an addition rate of 17.3 parts / hr while maintaining the internal temperature at 54 to 56 ° C., and the addition of ethyl acetate was stopped when the concentration of the (meth)acrylic resin reached 35% by mass, and the temperature was kept at this temperature until 6 hours had elapsed from the start of the addition of ethyl acetate. Finally, ethyl acetate was added to adjust the concentration of the (meth)acrylic resin to 20% by mass, and acrylic resin solution 2 was prepared. The weight average molecular weight Mw of the obtained acrylic resin was 1.6 million, and the molecular weight distribution Mw / Mn was 4.5. Note that Mw and Mn were measured using a GPC apparatus with a TSKgel GMH column manufactured by Tosoh Corporation. HR Two "-H(S)" were connected in series, and tetrahydrofuran was used as the eluent. The sample concentration was 2 mg / mL, the sample amount was 100 μL, the temperature was 40°C, and the flow rate was 1 mL / min. The measurements were performed in terms of standard polystyrene.
[0274] (3-2) Preparation of Pressure-Sensitive Adhesive Composition (2) To 100 parts of the solid content of the acrylic resin solution (2) obtained in (3-1), 0.15 parts on an active ingredient basis of (Mitsui Chemicals: product name "D-101E" (ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate (solid content concentration 75 mass%)) and 0.2 parts of a silane coupling agent (Shin-Etsu Chemical Co., Ltd.: product name "KBM-403") were added, and ethyl acetate was further added to adjust the solid content concentration to 13%, to obtain a pressure-sensitive adhesive composition (2).
[0275] (3-3) Preparation of adhesive sheet (2) The adhesive composition (2) prepared in (3-2) above was applied to the release-treated surface of a separate film made of a release-treated polyethylene terephthalate film [manufactured by Mitsubishi Chemical: MRV (V04) (thickness: 38 μm)] using an applicator so that the thickness after drying would be 15 μm, and an adhesive layer was prepared by drying for 1 minute at 100° C. Next, the surface of the obtained adhesive layer opposite the separator film was attached to the release-treated surface of a separate film made of a release-treated polyethylene terephthalate film [manufactured by Mitsubishi Chemical: MRF (thickness: 38 μm)] to prepare an adhesive sheet (2) as the adhesive layer (2).
[0276] <Preparation of optical laminate> Example 1 The substrate layer and the alignment layer on the 1 / 2 wavelength retardation layer side of the retardation plate A with the substrate layer prepared above were peeled off to expose the 1 / 2 wavelength retardation layer. The release film A on one side of the linear polarizing plate (1) prepared above was peeled off. The exposed 1 / 2 wavelength retardation layer and the polarizer (1) exposed by peeling off the release film A of the linear polarizing plate (1) were bonded together using the adhesive layer (1A) which is the first bonding layer. The bonding of the 1 / 2 wavelength retardation layer and the linear polarizing plate (1) was performed so that the angle between the slow axis of the 1 / 2 wavelength retardation layer and the transmission axis of the polarizer (1) was 15°. Next, the release film A on the other side was peeled off from the linear polarizing plate (1) to expose the polarizer (1). The exposed polarizer (1) was bonded to the adhesive layer of the surface protective film C. Next, the alignment layer and the base layer on the ¼ wavelength retardation layer side were peeled off to expose the ¼ wavelength retardation layer, and a pressure-sensitive adhesive layer (2) was attached to the exposed ¼ wavelength retardation layer to obtain an optical laminate (1). Each attachment surface was subjected to a corona treatment.
[0277] Example 2 An optical laminate (2) was obtained in the same manner as in Example 1, except that the linear polarizing plate (1) was replaced with the linear polarizing plate (2).
[0278] Example 3 An optical laminate (3) was obtained in the same manner as in Example 1, except that the pressure-sensitive adhesive layer (1B) was used as the first attaching layer instead of the pressure-sensitive adhesive layer (1A).
[0279] Example 4 An optical laminate (4) was obtained in the same manner as in Example 2, except that the pressure-sensitive adhesive layer (1B) was used as the first attaching layer instead of the pressure-sensitive adhesive layer (1A).
[0280] Example 5 An optical laminate (5) was obtained in the same manner as in Example 1, except that the pressure-sensitive adhesive layer (1C) was used as the first attaching layer instead of the pressure-sensitive adhesive layer (1A).
[0281] Example 6 An optical laminate (6) was obtained in the same manner as in Example 2, except that the pressure-sensitive adhesive layer (1C) was used as the first attaching layer instead of the pressure-sensitive adhesive layer (1A).
[0282] Example 7 An optical laminate (7) was obtained in the same manner as in Example 2, except that the pressure-sensitive adhesive layer (1D) was used as the first attaching layer instead of the pressure-sensitive adhesive layer (1A).
[0283] Example 8 The substrate layer (substrate C) on the first liquid crystal cured layer B side of the substrate layer-attached retardation plate B prepared above was peeled off to expose the alignment layer (photo-alignment film D). The release film A on one side of the linear polarizing plate (2) prepared above was peeled off. The exposed alignment layer (photo-alignment film D) and the polarizer (2) exposed by peeling off the release film A of the linear polarizing plate (2) were bonded together using the adhesive layer (1A) which is the first bonding layer. The retardation plate B and the linear polarizing plate (2) were bonded together such that the angle between the slow axis of the first liquid crystal cured layer B and the transmission axis of the polarizer (2) was 45°. Next, the release film A on the other side was peeled off from the linear polarizing plate (2) to expose the polarizer (2). The exposed polarizer (2) was bonded to the adhesive layer of the surface protective film C. Next, the substrate layer on the second liquid crystal cured layer B side was peeled off to expose the alignment layer (vertical alignment film), and the pressure-sensitive adhesive layer (2) was bonded to obtain an optical laminate (8). Each bonding surface was subjected to a corona treatment.
[0284] Comparative Example 1 The substrate layer and the alignment layer on the 1 / 2 wavelength retardation layer side of the retardation plate A with the substrate layer prepared above were peeled off to expose the 1 / 2 wavelength retardation layer. The exposed 1 / 2 wavelength retardation layer and the protective film B side of the linear polarizing plate (3) were attached using the adhesive layer (1A). The 1 / 2 wavelength retardation layer and the linear polarizing plate (3) were attached to each other so that the angle between the slow axis of the 1 / 2 wavelength retardation layer and the transmission axis of the polarizer (3) was 15°. Next, the peelable film A of the linear polarizing plate (3) was peeled off to expose the polarizer (3). The exposed polarizer (3) was attached to the adhesive layer of the surface protective film C. Next, the alignment layer and the substrate layer on the 1 / 4 wavelength retardation layer side were peeled off to expose the 1 / 4 wavelength retardation layer, and the adhesive layer (2), which is the second attachment layer, was attached to the exposed 1 / 4 wavelength retardation layer to obtain an optical laminate (9). Each attachment surface was subjected to a corona treatment.
[0285] The obtained optical laminate was subjected to the above-mentioned weather resistance test after peeling off and removing the surface protective film C together with the pressure-sensitive adhesive layer of the surface protective film C. The results are shown in Table 5. The obtained optical laminate was subjected to the above-mentioned edge swelling test after peeling off and removing the surface protective film C together with the pressure-sensitive adhesive layer of the surface protective film C. The results are shown in Table 6.
[0286] [Table 5]
[0287] [Table 6] [Explanation of symbols]
[0288] 1...Optical laminate 101...Polarizer 20…Retardation plate 201...First liquid crystal hardening layer 202…Second liquid crystal hardening layer 30a...first lamination layer 30b…Second lamination layer 30c...Third lamination layer 40...Image display element 109...Optical film including pressure-sensitive adhesive layer
Claims
1. An optical laminate including an optical film including a pressure-sensitive adhesive layer, a polarizer in which a dichroic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film, a first attachment layer, a retardation plate, and a second attachment layer in this order, the pressure-sensitive adhesive layer side of the optical film is in direct contact with the polarizer, The polarizer and the first attachment layer are in direct contact with each other, The layer constituted by the first bonding layer, the retardation plate, and the second bonding layer has an absorbance of 0.1 or more for light having a wavelength of 340 nm. Optical laminate.
2. The boron content of the polarizer is 0.5% by mass or more. The optical laminate according to claim 1 .
3. The luminosity-corrected single transmittance of the polarizer is 41% or more, The luminosity-corrected polarization degree of the polarizer is 99.5% or more. The optical laminate according to claim 1 or 2.
4. The retardation plate is made of a liquid crystal cured layer. The optical laminate according to claim 1 or 2.
5. The retardation plate is a λ / 4 retardation plate exhibiting reverse wavelength dispersion. The optical laminate according to claim 1 or 2.
6. The first attachment layer is a pressure-sensitive adhesive layer. The optical laminate according to claim 1 or 2.
7. The first bonding layer contains an ultraviolet absorbing agent. The optical laminate according to claim 1 or 2.
Citation Information
Patent Citations
Circularly polarizing plate, optical laminate, and image display device
JP2022101448A